Baseline levels and spatial distribution of arsenic species in surface sediments of the East China Sea shelf - Tianyu Bian; Xiaoyong Duan; Bin Chen; Xingliang He; Shenghua Lv; Meina Li; Ke Cao; Fei Gao; Ping Yin (Marine Pollution Bulletin, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

A multi-dimensional early warning model for coal and gas outburst risk based on microseismic monitoring with seismic velocity tomography-identified risk zones - Chao Zhou; Bo Li; Dazhao Song; Xueqiu He; Zhenlei Li; Liming Qiu; Yingjie Zhao; Shan Yin; Jintao Dang; Ping Wang (Journal of Applied Geophysics, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Inducing spin polarization in Cs2CuBr4 by Fe2+ doping for efficient photocatalytic aerobic toluene oxidation - Hao Zheng; Jinlin Yin; Ping Lu; Yi Lu; Xinyan Jiang; Shaoke Chen; Yifei Pan; Ning Zhang; Jin Wang; Zhengquan Li (Chemical Engineering Journal, 2026)

Immobilization Behavior of Mono- and Multi- Heavy Metals using Enzyme Induced Carbonate Precipitation - Chun Zhang; Ping Chen; Yi Bian; Yin Wang; Yuenan Li; Liangtong Zhan (Water, Air, & Soil Pollution, 2026)

Scleroglucan from Agroathelia rolfsii ameliorates glucolipid metabolic dysfunction in high-fat diet-fed mice and is associated with gut microbiota and metabolite changes - Dafang Yin; Kairui Tong; Min Zhou; Ping Yu; Mengfan Lyu; Mine Yang; Yanlong Wen; Lianghua Wen; Yang Li; Yadong Zhong; Jielun Hu (Food Research International, 2026)

Three-dimensional printed zerovalent iron enables selective and sustained reductive dehalogenation of florfenicol via structure-induced corrosion resistance and electron transfer regulation - Dan Li; Lu Liu; Haochen Li; Tao Ye; Junhong Wu; Jiaying Li; Si Zhai; Mengli Li; Huigai Wei; Lei Li; Jianhui Xu; Peng Liu; et al. (Environmental Research, 2026)

Erosion and entrainment in dry granular flows: Insights from large-scale experiments - Shi-lin Zhang; Yang Gao; Yue-ping Yin; Lonneke Roelofs; Wen-pei Wang; Xie-wen Hu; Bin Li (Engineering Geology, 2026)

Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A fully biomass-derived intrinsically flame-retardant phenolic resin: Robust adhesion, fire-safe coatings, and closed-loop upcycling for multifunctional cellulose fibers - Wei Tan; Lei Tan; Yin Tian; Ying Chang; Guixiang Song; Lu Bai; Ping Li; Yuanlin Ren; Xiaohui Liu (Chemical Engineering Journal, 2026)

Regenerated cellulose fibers functionalized with lignin-derived boron-containing phenolic networks for durable flame retardancy and UV protection - Wei Tan; Jieyun Zhao; Lei Tan; Yin Tian; Guixiang Song; Ying Chang; Lu Bai; Ping Li; Yuanlin Ren; Xiaohui Liu (Carbohydrate Polymers, 2026)

A divalent nanoparticle vaccine confers robust protective immunity against serotype O FMDV and SVA in pigs - Nan Cao; Yamei Li; Xinghua Chen; Hehai Li; Linxing Tian; Zihui Hu; Yin Bo; Feifei Diao; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Landscaping neurodevelopment of attention-deficit hyperactivity disorder - Ningning Liu; Yin-Shan Wang; Zi-Xuan Zhou; Peng Gao; Chongjing Luo; Xinyi Zhang; Ziqing Zhu; Yuan Gao; Fei Ren; Yan Zhu; Li-Zhen Chen; Haimei Li; et al. (Science Bulletin, 2026)

Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

Assessing cognitive impairment in epilepsy using Arterial spin-labeled (ASL) perfusion imaging - Qiuyan Chen; Jie Zhang; Rong Chen; Yameng Qin; Xu Wang; Qiang Liu; Zheng Yin; Ping Yang; Feng Rao; Longnan Wang; Mengyun Li; Yanzi Jin; et al. (Brain Imaging and Behavior, 2026)

Drivers of greenhouse gas emissions from global coastal blue carbon ecosystems: a synthesis of methane and carbon dioxide fluxes - Fei Wang; Xiaoyong Duan; Gang Tong; Xue Li; Ke Cao; Xingliang He; Bin Chen; Fei Gao; Ping Yin; Xianguo Li; Dahai Zhang (Acta Oceanologica Sinica, 2026)

Bioactive prenylated acylphloroglucinols from Hypericum scabrum - Li-Ping Teng; Jie-Lian Huang; Shui-Qing Guan; Chen-Xi Xin; Zi-Yin Mai; Yik-Ling Chew; Zhong-Bo Zhou; Gencheng Liang (Natural Product Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Acute topical menthol application and exercise performance: A systematic review and meta-analysis of perceptual and physiological responses - Yong Wang; Xiaohan Fan; Hansen Li; Xing Zhang; Mingyue Yin; Kai Xu; Yuming Zhong; Yilin Zhang; Juan Cui; Tianyu Song; Ping Liu; Hengzhi Deng (Journal of Thermal Biology, 2026)

Dual-functional Z‑scheme heterojunction nanozymes with surface encapsulation of porphyrin-based metal-organic framework on covalent organic framework for integrated detection and removal of aflatoxin B1 in foods - Birou Wang; Xiang Li; Xi Huang; Shucong Mo; Jia Yin; Bowen Chen; Yun Huang; Ping Du; Sufang He (Journal of Hazardous Materials, 2026)

Enhancement of anammox coupled arsenate reduction by coexisting iron-bearing minerals - Wentao Wang; Weiyi Xiong; Qing Jiang; Long-jun Ding; Ping Wang; Jiang-Shan Li; Hui Yin; Peng Cai (Journal of Hazardous Materials, 2026)

Long-range transported dust enhances ice nucleating particle abundance in the North China Plain - Yue Sun; Yujiao Zhu; Hengde Liu; Lanxiadi Chen; Hongyong Li; Yujian Bi; Di Wu; Xiangkun Yin; Can Cui; Ping Liu; Yu Yang; Jisheng Zhang; et al. (Journal of Environmental Sciences, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Stable isotope labeling LC–MS for profiling the amine submetabolome in a D-lactate treated cell model - Yue-Qiang Chen; Xiao-Xia Dong; Li Liu; Xiu-Ping Chen; Chen-Guo Feng; Li-Xing Zhan; Yue Su; Fang Zhang; Yin-Long Guo (Analytica Chimica Acta, 2026)

Synergistic effects of sequential ultrasound and autoclaving treatments on the structure, functionality, and digestibility of chestnut starch varieties - Yuan-Yuan Zhang; Can Xu; Ming-Xue Tu; Yin-Ping Zhang; Cong-Hu Li; Liang-Liang Zhu; Ting Hu (Food Chemistry, 2026)

Preparation of C and Co co-doped TiO2 Nanomaterials for Visible-Light Photocatalytic Antibacterial Activity - Chunhui Meng; Yuena Li; Qitong He; Yue Hao; Wenjun Yin; Huang Zhou; Ping Li (Water, Air, & Soil Pollution, 2026)

Integrating microbial functional traits to evaluate responses of soil quality to organic amendments in newly reclaimed farmland - Luotong Wang; Hanqin Yin; Chunlei Huang; Guifang Li; Cheng Zhu; Ping Li (Plant and Soil, 2026)

Paleoclimatic evolution of the northeastern Tibetan Plateau margin during the Late Oligocene-Early Miocene: Evidence from Ostracod shell trace elements - Wei Chen; Jinlong Ma; Xiaofeng Wang; Xuan Li; Liang Zeng; Xiaoqing Jiang; Ping Yang; Houyong Luo; Ke Yin (Journal of Mountain Science, 2026)

In-situ monitoring reveals the determinants of dissolved methane concentrations within seagrass meadows in a lagoon in northern China - Rui Jin; Xiaoyong Duan; Ping Yin; Xue Li; Bin Chen; Ke Cao; Shenghua Lv; Daolai Zhang; Xingliang He; Xianguo Li; Dahai Zhang (Acta Oceanologica Sinica, 2026)

Structural and dynamic insights into SPDT for phosphorus allocation in rice - Haitao He; Yan Liu; Jie Zhang; Xiaofeng Zheng; Lihuan Jiang; Zhangmeng Du; Jiaqi Zuo; Shuo Cao; Xuemei Peng; Zhiwen Zheng; Kun Li; Cuicui Shen; et al. (Science China Life Sciences, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Metabolites from Trichoderma amazonicum AF2115A by monoculture and coculture with Fusarium oxysporum A11F(B) - Wei-Cheng Xu; Yin-Ping Song; Ji-Xue Zou; Xiu-Li Yin; Nai-Yun Ji (Phytochemistry, 2026)

Mycorrhizal-association type mediates soil priming effect and its response to nitrogen addition in subtropical plantations - Wei Zhang; Xiao-Hong Wang; Liming Yin; Maokui Lyu; Lin-Qiao Jia; Li-Li Wang; Ai-Ping Liu; Xiao-Die Hu; Xiaodong Yao; Guang-Shui Chen (Pedobiologia, 2026)

Corrigendum to “Sulfide-based denitrification of ship wastewater: Core bacteria succession and metabolic mechanism with different sulfite loadings” [J. Environ. Chem. Eng. 14 (2026) 122365] - Shuai Zhao; Wei Li; Ruonan Xin; Sini Zhou; Jianhua Wang; Lingxiao Lv; Yin Liu; Nan Li; Ping Guo (Journal of Environmental Chemical Engineering, 2026)

Sulfide-based denitrification of ship wastewater: Core bacteria succession and metabolic mechanism with different sulfite loadings - Shuai Zhao; Wei Li; Ruonan Xin; Sini Zhou; Jianhua Wang; Lingxiao Lv; Yin Liu; Nan Li; Ping Guo (Journal of Environmental Chemical Engineering, 2026)

Sediment physicochemical and dissolved organic matter control microbial responses and nitrous oxide emissions across a coastal wetland transition from invasion to reclamation - Shengwei Cao; Yaci Liu; Ping Yang; Xiujian Hu; Yan Dong; Xiangyu Guan; Ping Yin; Yasong Li (Journal of Environmental Management, 2026)

TGase-induced WPI-GA microgels for stabilized HIPEs and encapsulation probiotics with enhanced thermal stability and gastrointestinal survival - Yaxin Yin; Yingnan Zou; Chin Ping Tan; Deyang Li; Xiaojiao Zheng; Daodong Pan; Maolin Tu (Food Hydrocolloids, 2026)

Associations between antibiotic and metal resistance genes in geothermal springs - Zhipeng Yin; Hua Ping; Cheng Li (Environmental Research, 2026)

Reversible dormancy via gradient cooling ensures high survival and muscle quality through coordinated metabolic suppression and recovery in Litopenaeus vannamei - Yueqin Li; Ping Zhang; Ziyi Yin; Yuwei Zhang; Qiwei Du; Zhen Wu; Xiaoqun Zeng; Daodong Pan (Food Bioscience, 2026)

Synergistic inspiration of in situ growth technology and biomass phytic acid for designing durable flame retardant and antibacterial cellulose fibers - Yin Tian; Wei Tan; Lu Bai; Lei Tan; Ying Chang; Guixiang Song; Ping Li; Yuanlin Ren; Xiaohui Liu (Carbohydrate Polymers, 2026)

Plant–microbe interactions underpin contrasting enzymatic responses to flooding intensity variation in the cascade reservoir riparian areas - Nan-ping Wu; Shan-ze Li; Kailang Yin; Yu-chun Wang; Zheng Sun; Xuming Xu; Qingkong Chen; Yufei Bao; Jie Wen (CATENA, 2026)

New α-pyranone derivatives from Diaporthe sp. WLM-Y1 - Xiang Li; Xue-Kai Zhao; Xu-Ping Zhang; Wei-Guang Wang; Qian-Qian Yin; Lu Gao (Natural Product Research, 2026)

New perspectives on key bioactive molecules of lactic acid bacteria: integrating targeted screening, key gene exploration and functional evaluation - Shi Hu; Qi Wang; Jinfeng Wu; Hangjia Zhang; Jiaqi Yin; Lina Ding; Ping Li; Hang Xiao; Qing Gu; Jiarun Han (Critical Reviews in Food Science and Nutrition, 2026)

Transcriptomic and physiological responses of Epinephelus akaara to chronic cold stress - Jichun Li; Huilai Shi; Suzhen Ran; Jianshe Zhang; Xiaolong Yin; Hongling Ping; Tao Zhang; Jiji Li; Bin Li; Yingying Ye (Aquaculture, 2026)

Controls on heavy metal variability in a coastal mountainous river: Impacts of tides, typhoons, and anthropogenic activities - Yalong Li; Ni Su; Yun Zhao; Ergang Lian; Chao Li; Juan Xu; Ping Yin; Shouye Yang (Journal of Geochemical Exploration, 2026)

Effects of three freezing treatments on the quality of frozen chow mein noodles - Pengyuan Tian; Ping Jiang; Ming Liu; Naijuan Wang; Lijuan Zhang; Sijia Xu; Peng Yin; Weiqing Zhang; Mingfu Yu; Dan Li (Journal of Cereal Science, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Correction: Modulation of the immune response by focused ultrasound suppressed brain abscess formation - Zhuo-Hao Liu; Nan-Yu Chen; Chiung-Yin Huang; Ya-Jui Lin; Ping K. Yip; Kuo-Chen Wei; Hao-Li Liu (Drug Delivery and Translational Research, 2026)

Modulation of the immune response by focused ultrasound suppressed brain abscess formation - Zhuo-Hao Liu; Nan-Yu Chen; Chiung-Yin Huang; Ya-Jui Lin; Ping K. Yip; Kuo-Chen Wei; Hao-Li Liu (Drug Delivery and Translational Research, 2026)

Iron: A double-edged sword of female reproductive health - Rui Mao; Dan Yin; Wenbo Lv; Die Wang; Ying Ouyang; Cuilan Zhou; Jun Liu; Suyun Li; Yunhua Zhu; Ping Yu; Hongqing Liao; Cuiying Peng (Journal of Trace Elements in Medicine and Biology, 2026)

Behavioral toxicity of tralopyril in Oryzias melastigma: Integrated consequences of multi-organ damage and thyroid hormone dysregulation - Bin Liu; Tengzhou Li; Bianhao Zeng; Haiyang Yin; Le Sun; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Tracing monomethylmercury origins in planktivorous migratory fish in the coastal East China Sea: Evidences from mercury and carbon stable isotopes - Chenxi Zou; Rui Wang; Ping Li; Shaochen Yang; Haiyu Yan; Daqiang Yin (Journal of Hazardous Materials, 2026)

Fabrication of multifunctional cellulose aerogel materials with one-dimensional (fiber), two-dimensional (film), and three-dimensional (structure) structures based on ambient drying technology - Lei Tan; Wei Tan; Yin Tian; Guixiang Song; Ying Chang; Ping Li; Yuanlin Ren (Chemical Engineering Journal, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Molecular Responses of Cold Stress Adaptation in the Red Grouper (Epinephelus Akaara): Compensatory Regulation Between FOXO and MAPK Signaling Pathways - Bin Li; Jichun Li; Hongling Ping; Tao Zhang; Jie He; Suzhen Ran; Jianshe Zhang; Xiaolong Yin; Yingying Ye; Huilai Shi; Jiji Li (Marine Biotechnology, 2026)

Hydrothermal integration and synergy regulate carbon exchange in forest ecosystems of eastern China - Yin Wang; Xiaojuan Tong; Jinsong Zhang; Jun Li; Ping Meng; Weifeng Wang; Yating Wang; Mingxin Yang; Qingyuan Liu (Agricultural and Forest Meteorology, 2026)

The bactericidal efficacy of carvacrol against drug-resistant Streptococcus iniae and its protective effects on channel catfish (Ictalurus punctatus) - Lizi Yin; Minmin Wang; Jianing Wu; Xiaonan Li; Fen Chen; Bowen Liu; Yi Geng; Xiaoli Huang; Defang Chen; Ping Ouyang (Aquaculture, 2026)

Interspecific interactions increase soil aggregate stability through altered root traits in long-term legume/maize intercropping - Xiao-Yang Duan; Surigaoge Surigaoge; Yu-He Du; Dai-Han Fu; Hao Yang; Xin Yang; Huai-Yin Ma; Hu Zhou; Peter Christie; Dario Fornara; Wei-Ping Zhang; Long Li (Soil and Tillage Research, 2026)

Algae: A considerable regulator of methylmercury in mercury-contaminated paddy fields - Ling Su; Guangjun Luo; Tianrong He; Pan Wu; Ping Li; Deliang Yin; Yuping Xiang; Xian Zhou (Journal of Environmental Sciences, 2026)

High-resolution mapping decouples hydrodynamic sorting and sediment transport as primary drivers of PAH distribution in the East China Sea inner shelf - Xiaoyong Duan; Ping Yin; Ke Cao; Fei Gao; Bin Chen; Meina Li; Shenghua Lv; Xiaoying Chen (Environmental Pollution, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Development of an integrated searching system for rapid and accurate classification of edible oils by matrix-assisted laser desorption/ionization mass spectrometry - Michael Ho-Yin Ma; Suying Li; Zhen-Yan Li; Jessie Wing-Yin Wu; Zhong-Ping Yao (Analytica Chimica Acta, 2026)

Innovative design of CXCR4 cyclic peptide via molecular docking for 99mTc-Labeled SPECT/CT imaging in melanoma - Xianrui Yin; Xin Wang; Chengwei Chen; Shenglan Jia; Wanhong Li; Yihong Wu; Xin Chen; Danling Feng; Wai Ping Cecilia Tsang; Zhihao Han; Yueqing Gu (Analytica Chimica Acta, 2026)

Synthetic peptide vaccines targeting SVA elicit robust protective immune responses in swine - Yamei Li; Nan Cao; Bo Yin; Mingfang Ji; Xiangzu Liu; Shudan Liu; Mingjin Jiao; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Quercetin alleviates ethanol-induced hepatocyte senescence by interacting with glycinamide ribonucleotide transformylase - Chen Huimin; Peng Shufen; Cui Zhaoyu; Liu Jiaxin; Chen Li; Yin Xingzhu; Wu Bangfu; Zhao Ying; Wang Yu; Mo Li; Liang Chanhua; Li Dongyan; et al. (Food Research International, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

Molecular mechanism of Tralopyril-induced enteritis in Pacific oyster (Crassostrea gigas) through multi-pathway modulation: Network toxicology and experimental validation - Ping Li; Chang Liu; Minghao Yin; Xu Wang; Chengzhuang Chen; Ling Liu; Zhi-Hua Li (Pesticide Biochemistry and Physiology, 2025)

Microplastic aging and plastisphere succession in mangrove sediments: Mechanisms, microbial interactions, and degradation potential - Yuanyuan Su; Jun Lei; Xiaoping Diao; Licheng Peng; Lianzheng Yin; Yongqiang Qin; Wen Zhang; Ping Li (Journal of Hazardous Materials, 2025)

Synergistic coupling of Pd@PtRh nanozyme with NiMn2O4/In2S3 Z-scheme heterojunction for ultrasensitive photoelectrochemical sensing of malathion - Rui-Jin Shao; Ke Yin; Lei Zhao; Yadong Xue; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

The role of TLR4/NF-kB signaling axis in pneumonia: from molecular mechanisms to regulation by phytochemicals - Jun Yin; Jianxiang Huang; Ping Zhou; Linwei Li; Qin Zheng; Hong Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

A comprehensive review of thermal comfort related design strategy of semi-outdoor transitional spaces - Guoying Hou; Yiming Kuai; Lige Yin; Yuan Li; Ping Shu (Energy and Buildings, 2025)

Therapeutic effects of Scutellaria baicalensis total flavonoids on metabolic syndrome in rats via modulation of PPARα and PPARγ signaling - Yang Zhou; Zhi-Ping Li; Yu-Hang Lian; Xin Gao; Song-He Yin; Yu-Mei Zhao (Journal of Molecular Histology, 2025)

Impact of Phosphate Solubilizing Bacterial Agent on Cadmium Bioavailability and Microbial Communities in Soil and Cd Accumulation in Lettuce Plants - Yue Yu; Ping Li; Yanhong Wang; Xinzhe Lu; Chunlei Huang; Hanqin Yin (Journal of Earth Science, 2025)

Rice-duck farming enhances phosphorus use and grain yield via altering soil phosphorus fractions in the Yangtze River Delta of eastern China - Hui Gao; Qingnan Chu; Xiangyu Liu; Liang Zheng; Shuhan Xu; Linkui Cao; Detian Li; Shuai Yin; Ping He; Chengrong Chen; Zhimin Sha (Agriculture, Ecosystems & Environment, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Fragments of ancient continental lithospheric mantle in the Mogok metamorphic Belt, Northern Myanmar: Re–Os isotope and platinum group element constraints - Qing-Hua Zhang; Bin Su; Yi Chen; Victoria Pease; Tou-Ping Peng; Zhu-Yin Chu; Yi-Bing Li; Kai-Hui Shi; Si Chen (Precambrian Research, 2025)

Tracing mercury sources and transfer pathways in Pacific and Atlantic Ocean tuna and billfish using mercury stable isotopes - Ruo Lan; Feng Wu; Jingqian Xie; Shaochen Yang; Xingyu Liang; Zhiyang You; Ping Li; Runsheng Yin; Xinbin Feng (Journal of Hazardous Materials, 2025)

Quantifying the major sources of nitrate in PM2.5 in a port city in southeastern China: Perspectives from nitrate dual isotopes and NOx emission inventory - Qi-Yu Miao; Xiang Li; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Xi-Jie Yin (Atmospheric Pollution Research, 2025)

Deciphering dissolved inorganic carbon dynamics in Xiangshan Bay: isotopic constraints on sources, hydrodynamic controls, and anthropogenic influences - Xue Li; Xiaoyong Duan; Gang Tong; Ping Yin; Fei Gao; Ke Cao; Bin Chen (Acta Oceanologica Sinica, 2025)

Erratum to “Coupling of Sulfate Reduction and Dissolved Organic Carbon Degradation Accelerated by Microplastics in Blue Carbon Ecosystems” [Water Research, 279, (2025), 123414] - Heli Wang; Yin Zhong; Qian Yang; Jiaying Li; Dan Li; Junhong Wu; Sen Yang; Jiashuo Liu; Yirong Deng; Jianzhong Song; Ping'an Peng (Water Research, 2025)

Dose-dependent effects of MIL-88A(Fe) and MIL-101(Fe) on arsenic immobilization and phytoremediation using ramie (Boehmeria nivea L.) - Jian Ye; Xingyan Yin; Chunping Yang; Xiaofei Tan; Chuang Li; Gaobin Chen; Ping Chen; Qiang Chen; Mingyang Dai (Chemical Engineering Journal, 2025)

A Novel Selenite-Reducing Bacterium Bacillus pseudomycoides SA14 Isolated from Se-Enriched Soil and Its Potential Se Biofortification on Brassica chinensis L. - Xianxin Huang; Yanhong Wang; Helin Wang; Xinyan Shi; Chunlei Huang; Hanqin Yin; Yixian Shao; Ping Li (Journal of Earth Science, 2025)

Coupling of sulfate reduction and dissolved organic carbon degradation accelerated by microplastics in blue carbon ecosystems - Heli Wang; Yin Zhong; Qian Yang; Jiaying Li; Dan Li; Junhong Wu; Sen Yang; Jiashuo Liu; Yirong Deng; Jianzhong Song; Ping'an Peng (Water Research, 2025)

Long-term settlement of deepsea pipelines on a soft clayey seabed: Poro-elasto-viscoplastic modeling - Jun Cheng; Jian Li; Fu-Ping Gao; Zhen-Yu Yin (Ocean Engineering, 2025)

Bioremediation potential of sulfadiazine-degrading bacteria: Impacts on ryegrass growth and soil functionality - Minghao Yin; Ping Li; Chengzhuang Chen; Ruolan Jia; Banghua Xia; Yiwei Liu; Aiqiu Liu; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Impact of the Yangtze River on Sediment source-to-sink processes in estuarine bays: a study of the Oujiang River Estuary, SE China - Xia Guang; Ping Yin; Ke Cao; Fei Gao; Yuan Tian; Xiangtong Huang; Bin Chen; Meina Li; Jinqing Liu (Frontiers in Marine Science, 2025)
Our study was designed to unravel the provenance signals of sediments from various sediment source-to-sink processes. To achieve this, we systematically collected samples from river basins, estuaries, and offshore waters of the Oujiang River estuary. Analyses of clay minerals and trace geochemical elements (Cr, Th, Sc) were then conducted. Our findings revealed a dynamic pattern of sediment distribution, with the predominant clay minerals in the surface sediment of the offshore area being illite, followed by kaolinite and chlorite, with a minor smectite content. Notably, we observed a gradual increase in the proportions of illite and smectite from the upstream to the estuary, while kaolinite decreased accordingly. The ratios of Cr/Th and Sc/Th in the small mountain rivers also showed a gradual increase, indicating a rising influence of fine-grained sediment from the Yangtze River. Furthermore, we utilized a robust nonlinear mathematical model to determine and quantify the sources and provenance contributions of the clay fraction sediment in the Oujiang River estuary. Our model results revealed that the majority (64%) of the clay fraction sediment in the offshore region of the estuary originates from the Yangtze River. In contrast, sediments from small mountain rivers, including the Oujiang River, contribute an average of 29%, but this can increase to 40% within the Oujiang River estuary and its southern areas. Coastal currents and tides influence the sediment distribution in coastal areas. The Zhe-Min Coastal Current plays a significant role in transporting sediments from the Yangtze River to the estuaries of Zhejiang Province, where they settle in the downstream areas of the current. Moreover, sediment from the Oujiang River is carried southward by the coastal current, most of which is deposited in the estuary and the nearby coastal waters to the south. In conclusion, our study underscores the significant influence of sediments from the Yangtze River on the surface sediments in small mountain rivers and offshore regions near the Zhejiang coastline.

Genetic deletion of microRNA-15a/16-1 in pericytes stimulates cerebral angiogenesis and promotes functional recovery after ischemic stroke - Ping Sun; Yang Xu; Tianqing Xiong; Shun Li; Na Qiu; Chao Zhou; Jiefei Wang; Alexander Chang; Uma R. Chandran; Ke-Jie Yin (Angiogenesis, 2025)

The methane-sulfate transition interface in offshore sediments serves as a critical boundary for abrupt transitions in sedimentary environments - Xue Li; Xiaoyong Duan; Ping Yin; Ke Cao; Xingliang He; Jianghai Yang; Bin Chen (Marine and Petroleum Geology, 2025)

Fate of polystyrene micro- and nanoplastics in zebrafish liver cells: Influence of protein corona on transport, oxidative stress, and glycolipid metabolism - Ling Liu; Yanan Xu; Yuqing Ma; Fengshang Duan; Cunlong Wang; Jianxue Feng; Haiyang Yin; Le Sun; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Effects of eugenol–tricaine composite anesthesia on live transportation of Chinese mitten crab (Eriocheir sinensis) - Lele Leng; Ping Zhang; Ziyi Yin; Kexiang Li; Hang Li; Xiaoqun Zeng; Yangying Sun; Daodong Pan (Food Bioscience, 2025)

Quality decline of prepared dishes stored at 4 °C: Microbial regulation of nitrite and biogenic amine formation - Jiaxin Liu; Yin Wang; Ping Yang; Hongbo Li; Haizhen Mo; Prince Chisoro; Dong Han; Chunhui Zhang (Food Microbiology, 2025)

Roseateles cavernae sp. nov., a Bacterium Isolated from Freshwater of the Old Huanglong Cave in Yunnan Province, South-West China - Yu-Man Zhang; Qian Jiang; Mu-Yao Li; Qing-Yu Miao; Yi-Qing Li; Min Yin; Cui-Ping Miao; Shu-Kun Tang (Current Microbiology, 2025)

A safety and absolute activity measurement method for Phi29 DNA polymerase based on chemiluminescent detection of dATP consumption - Xuefeng Wang; Ping Gui; Xiao Li; Feng Lu; Wei Jing; Changlong Li; Zelin Lu; Yanna Lin; Huancai Yin; Haichao Li; Fuqiang Ma (Analytica Chimica Acta, 2025)

Five undescribed chromone-phenylpyridone hybrids from Cineraria repanda-derived Penicillium oxalicum with cytotoxic and antibacterial activity - Yu Wei Huang; Jing Guan; Yin Tang; Ren Xiang Tan; Li Ping Lin (Phytochemistry, 2025)

Tracing the Changjiang-derived sediments along the southeast coast of China during the Holocene - Yalong Li; Xin Shan; Xiangtong Huang; Zhanghua Wang; Jianhua Gao; Ping Yin; Quanhong Zhao; Juan Xu; Zhen Song; Shouye Yang (Global and Planetary Change, 2025)

Root exudates drive root avoidance of maize in response to neighboring wheat - Xiao-Tong Yin; Fang-Fang Zhang; Rui-Peng Yu; Na Liu; Wei-Ping Zhang; Dario Fornara; Liesje Mommer; Xue-Xian Li; Long Li (Plant and Soil, 2025)

Raman spectroscopy coupled with chemometrics for identification of adulteration and fraud in muscle foods: a review - Haiyang Ma; Jiajun Guo; Guishan Liu; Delang Xie; Bingbing Zhang; Xiaojun Li; Qian Zhang; Qingqing Cao; Xiaoxue Li; Fang Ma; Yang Li; Guoling Wan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Deciphering denitrification drivers in a high‑nitrogen estuary: Insights from stable isotope analysis and microbial molecular techniques - Shengwei Cao; Ping Yin; Chunlei Liu; Xiujian Hu; Yaci Liu; Yuewen Zhao; Xiangyu Guan; Yasong Li (Science of The Total Environment, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Greenhouse gas fluxes and their determining factors in salt marsh wetlands along the south shore of Hangzhou Bay, East China Sea - Fei Wang; Xiaoyong Duan; Gang Tong; Xue Li; Ke Cao; Xingliang He; Bin Chen; Fei Gao; Ping Yin; Xianguo Li; Dahai Zhang (Journal of Environmental Management, 2025)

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Metabolomics-based mechanistic insights into antioxidant enhancement in mango juice fermented by various lactic acid bacteria - Shuai Liu; Yu-Jia Peng; Wei-Wei He; Xiao-Xiao Song; Yu-Xin He; Xiao-Yi Hu; Shui-Gen Bian; Yu-Hao Li; Jun-Yi Yin; Shao-Ping Nie; Ming-Yong Xie (Food Chemistry, 2025)

A smartphone-integrated bimetallic ratiometric fluorescent probe for specific visual detection of tetracycline antibiotics in food samples and latent fingerprinting - Yin-Xia Sun; Bo-Tao Ji; Jiang-Hai Chen; Li-Ping Liu; Lu-Lu Gao; Zhe-Peng Deng; Yu Sun; Jian-Jun Wang; Biao Zhao; Jin-Guo Li (Food Chemistry, 2025)

Biotransport and toxic effects of micro- and nanoplastics in fish model and their potential risk to humans: A review - Yanan Xu; Ling Liu; Yuqing Ma; Cunlong Wang; Fengshang Duan; Jianxue Feng; Haiyang Yin; Le Sun; Zhihan Cao; Jinho Jung; Ping Li; Zhi-Hua Li (Aquatic Toxicology, 2025)

Comparative chloroplast genomic analysis of an important horticultural plant, Dendrobium sulcatum (Orchidaceae) and phylogenetic position in Dendrobium - Feng-Ping Zhang; Jia-Jun Deng; Ying Guo; Li-Jun Han; Zi-Li Yin (Horticulture, Environment, and Biotechnology, 2025)

Study of the mechanism by which Bacillus subtilis improves the soil bacterial community environment in severely saline-alkali cotton fields - Hanji Xia; Hongguang Liu; Ping Gong; Pengfei Li; Qiang Xu; Qian Zhang; Mingyue Sun; Qiang Meng; Fuhai Ye; Weizhen Yin (Science of The Total Environment, 2025)

Analysis of carbon reduction potential from typical municipal solid waste incineration plants under MSW classification - Chenqi Gao; Rongxing Bian; Ping Li; Chengyue Yin; Xiao Teng; Jinran Zhang; Shudan Gao; Yating Niu; Yingjie Sun; Yanan Wang; Huawei Wang (Journal of Environmental Management, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

Nonlinear dynamic response of graphene platelets reinforced cylindrical shells under moving loads considering initial geometric imperfection - Yin-Ping Li; Gui-Lin She (Engineering Structures, 2025)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Effects of single or combined exposure to tralopyril and ocean acidification on energy metabolism response and sex development in Pacific oysters (Crassostrea gigas) - Ping Li; Minghao Yin; Xu Wang; Ruolan Jia; Chengzhaung Chen; Bin Liu; Yiwei Liu; Bianhao Zeng; Tengzhou Li; Ling Liu; Hong-Jun Song; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Corrigendum to “Mechanisms of eco-corona effects on micro(nano)plastics in marine medaka: Insights into translocation, immunity, and energy metabolism” [J Hazard Mater Vol 480, 2024, 136236] - Ling Liu; Yuqing Ma; Yanan Xu; Bin Liu; Cunlong Wang; Jianxue Feng; Mingyang Li; Haiyang Yin; Le Sun; Ping Li; Zhihua Li (Journal of Hazardous Materials, 2024)

Mechanisms of eco-corona effects on micro(nano)plastics in marine medaka: Insights into translocation, immunity, and energy metabolism - Ling Liu; Yuqing Ma; Yanan Xu; Bin Liu; Cunlong Wang; Jianxue Feng; Mingyang Li; Haiyang Yin; Le Sun; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2024)

Environmental behavior and toxic effects of micro(nano)plastics and engineered nanoparticles on marine organisms under ocean acidification: A review - Ling Liu; Haiyang Yin; Yanan Xu; Bin Liu; Yuqing Ma; Jianxue Feng; Zhihan Cao; Jinho Jung; Ping Li; Zhi-Hua Li (Environmental Research, 2024)

Effects of nanoplastics on the growth, transcription, and metabolism of rice (Oryza sativa L.) and synergistic effects in the presence of iron plaque and humic acid - Xiaoxue Ouyang; Jie Ma; Bingcong Feng; Yong Liu; Ping Yin; Xiaoyu Zhang; Pan Li; Qiusheng Chen; Yujie Zhao; Liping Weng; Yongtao Li (Environmental Pollution, 2024)

Genome-wide identification and biochemical characterization of glycoside hydrolase gene family members in Tilletia Horrida - Xinyue Shu; Yuping Zhong; Xiaoqun Yi; Aijun Wang; Ping Li; Desuo Yin; Aiping Zheng (Molecular Biology Reports, 2024)

Characteristics of surface air quality over provincial capital cities in Northwestern China during 2013–2020 - Dipesh Rupakheti; Sushma Dhital; Maheswar Rupakheti; Xiufeng Yin; Ping Li; Sishir Dahal; Benzhong Zhang (Journal of Atmospheric Chemistry, 2024)

Description and genomic characterization of Cohnella caldifontis sp. nov., isolated from hot springs in Yunnan province, south-west China - Ming-Xian Xiang; Cui-Ping Miao; Dian-Yan Zhang; Juan Wang; Yi-Qing Li; Min Yin; ShuKun Tang (Antonie van Leeuwenhoek, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Enhanced release of volatile halocarbons of microalgae in response to antibiotic-induced stress: Based on laboratory and ship-field experiments - Xiao-Yu Zhang; Li-Jing Yin; Xiao-Ping Lang; Zhen He; Gui-Peng Yang (Marine Environmental Research, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Association of Plasma Metal Levels with Outcomes of Assisted Reproduction in Polycystic Ovary Syndrome - Dan Yin; Rui Mao; Die Wang; Ping Yu; Cuilan Zhou; Jun Liu; Suyun Li; Yulin Nie; Hongqing Liao; Cuiying Peng (Biological Trace Element Research, 2024)

Tissue-Specific Toxicity in Common Carp (Cyprinus carpio) Caused by Combined Exposure to Triphenyltin and Norfloxacin - Yiwei Liu; Luoxin Li; Siqi Zhang; Minghao Yin; Tengzhou Li; Bianhao Zeng; Ling Liu; Ping Li; Zhihua Li (Fishes, 2024)
Triphenyltin (TPT) is a commonly encountered organotin compound known for its endocrine-disrupting properties; it frequently interacts with antibiotics in aquatic environments. In this study, common carp (Cyprinus carpio) (17.43 ± 4.34 g, 11.84 ± 0.88 cm) were chosen as the experimental organisms. According to the environmental concentration in the heavily polluted area, the control group and the experimental groups were exposed for 21 days to the following treatments: 1 μg/L TPT, 1 mg/L NOR, and a combination of 1 μg/L TPT plus 1 mg/L NOR. The investigation examined the individual and combined toxicities of TPT and norfloxacin (NOR) on the gill, liver, and gut tissues of common carp in highly polluted areas. The findings revealed tissue-specific variations in 1L-1β enzyme activity; specifically, 1L-1β enzyme activity exhibited a significant reduction in liver tissue under both NOR exposure and combined exposure, indicating that high concentrations of NOR had the most pronounced impact on the immune system of liver tissue. Furthermore, the gene expression levels of IL-1β, Lysozyme-C, NKA, and CPT1 in the liver, intestinal, and gill tissues showed differences after exposure. In addition, TPT exerted the most significant effect on intestinal tissue, followed by the liver and gill tissues. Interestingly, when TPT and NOR were exposed together, the toxic effects on all tissues were reduced, suggesting the existence of antagonistic effects.

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Aged polystyrene microplastics exposure affects apoptosis via inducing mitochondrial dysfunction and oxidative stress in early life of zebrafish - Ping Ding; Chongdan Xiang; Qian Yao; Xintong Li; Jiayi Zhang; Renli Yin; Lijuan Zhang; Adela Jing Li; Guocheng Hu (Journal of Environmental Management, 2024)

Neurobehavioral toxicity induced by combined exposure of micro/nanoplastics and triphenyltin in marine medaka (Oryzias melastigma) - Peiran Lin; Ling Liu; Yuqing Ma; Renyan Du; Chuansen Yi; Ping Li; Yanan Xu; Haiyang Yin; Le Sun; Zhi-Hua Li (Environmental Pollution, 2024)

Four dodecanoic acid derivatives from the cold-seep-derived fungus Cladosporium cladosporioides 8-1 - Chang-Peng Li; Yin-Ping Song; Xiao-Rui Liang; Nai-Yun Ji (Natural Product Research, 2024)

Contamination status, source analysis and exposure assessments of quinolone antibiotics in the south of Yancheng Coastal Wetland, China - Yaru Li; Zongshan Zhao; Daolai Zhang; Biying Li; Ping Yin (Environmental Geochemistry and Health, 2024)

Electrical structure identification of deep shale gas reservoir in complex structural area using wide field electromagnetic method - Zhi-Wen Gu; Yue-Gang Li; Chang-Heng Yu; Zhong-Ping Zou; Ai-Guo Hu; Xue-Bo Yin; Qinag Wang; Heng Ye; Zhang-Kun Tan (Applied Geophysics, 2024)

Exploring seasonal variations, assembly dynamics, and relationships of bacterial communities in different habitats of marine ranching - Cheng-Zhuang Chen; Ming-Hao Yin; Lin-Jing Niu; Jin-Xin Wang; Ling Liu; Yong-Jun Sun; Wen-Ming Ju; Ping Li; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Effects of miR-204-5p and Target Gene EphB2 on Cognitive Impairment Induced by Aluminum Exposure in Rats - Wei Liu; Jie Gao; Niping Hao; Jing Li; Jing Pei; Danfeng Zou; Shuo Yang; Yuhua Yin; Xiaoming Yang; Ping Mu; Lifeng Zhang (Biological Trace Element Research, 2024)

Comparative plastomes of eight subgenus Chamaesyce plants and system authentication of Euphorbiae Humifusae Herba - Long Wang; Ziting Huo; Wenbo Xu; Peina Zhou; Wenxiang Nan; Huijun Guo; Qianwen Zhang; Peng Yang; Raphael N. Alolga; Xiaojian Yin; Ping Li; Xu Lu (Food Chemistry, 2024)

Sulfur doping-induced morphological and electronic structure modification of polyoxometalate FeWO4 for enhanced removal of organic pollutants from water - Dong-Hua Xie; Wen-Qiang Li; Nuo Xu; Li Yuan; Wen-Hua Zhang; Tian-Yin Huang; Guo-Ping Sheng (Water Research, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

The effect of elevation, latitude, and plant richness on robustness of pollination networks at a global scale - Xiang-Ping Wang; Jeff Ollerton; Kit S. Prendergast; Jin-Chao Cai; Ma-Yin Tong; Miao-Miao Shi; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu (Arthropod-Plant Interactions, 2024)

Dynamic energy evolution and fragmentation characteristics of damaged rock under impact compression loading - Qiang-Qiang Zheng; Jia-Wei Qian; Ping-Feng Li; Zhi-Qiang Yin; Huan-Ting Zhao (Applied Geophysics, 2024)

A new lanostane-type triterpenoid from the marine shellfish symbiotic fungus Ceriporia lacerata CD7-5 - Sheng-Tao Fang; Feng-Ping Miao; Xiu-Li Yin; Nai-Yun Ji (Natural Product Research, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Enhanced Cr(VI) elimination from water by goethite-impregnated activated carbon coupled with weak electric field - Bing Li; Weiquan Li; Qian Zuo; Weizhao Yin; Ping Li; Jinhua Wu (Environmental Research, 2024)

The relationships between vertical variations of shallow gas and pore water geochemical characteristics in boreholes from the inner shelf of the East China Sea - Xue Li; Xiaoyong Duan; Xingliang He; Yongqing Xie; Lei Yang; Ping Yin; Ke Cao; Bin Chen; Fei Gao; Feng Li (Frontiers in Marine Science, 2024)
Shallow gas was widely recognized in the coastal region, especially in the estuarine delta areas with high organic matter (OM) burial flux. In this study, the vertical variations of shallow gas and the related geochemical indicators from two boreholes in the coastal region of the East China Sea (ECS) were investigated. Two gas-bearing layers were identified in the sediments from the Holocene and late Pleistocene series. Both boreholes exhibit a “typical” and an “inverse” Sulfate Methane Transition Zone (SMTZ). The “typical” SMTZs (SMTZ1 and SMTZ3) were in the upper part of the gas-bearing layers, where sulfate levels decrease and methane levels increase with depth. Conversely, the “inverse” SMTZs (SMTZ2 and SMTZ4) were in the lower part of the gas-bearing layers, exhibiting an increase in sulfate levels and a decrease in methane levels with depth, a phenomenon rarely documented in previous research. The downward variations of pore water geochemical characteristics indicates that these ions were related to Anaerobic Oxidation of Methane (AOM) processes. The increase in Ca 2+ and Ba 2+ concentrations and the gradual decrease in sulfate at the SMTZ reflect a series of biogeochemical processes resulting from the dissolution of carbonate and other minerals by AOM. The research indicates that sulfate in AOM may originate from multiple sources. Through analyzing the vertical distribution of shallow gas and the geochemical properties of pore water, this study elucidates the shallow gas formation mechanism and the features of the SMTZ, laying the groundwork for further investigations.

Induced Mesenchymal Stem Cells-Small Extracellular Vesicles Alleviate Post-stroke Cognitive Impairment by Rejuvenating Senescence of Neural Stem Cells - Jiayuan Liu; Li Peng; Lingwei He; Tianyue Yin; Yuhao Du; Mengmeng Yang; Ping Wu; Jun Li; Jiangbing Cao; Hongrui Zhu; Sheng Wang (Journal of Molecular Neuroscience, 2024)

Promoted iron corrosion and subsequent hexavalent chromium removal in zero-valent iron systems by oxidant activation - Weiting Chen; Bing Li; Weizhao Yin; Weilong Zeng; Ping Li; Jinhua Wu (Chemosphere, 2024)

Ocean acidification alters shellfish-algae nutritional value and delivery - Ruolan Jia; Minghao Yin; Xue Feng; Chengzhuang Chen; Chunfeng Qu; Ling Liu; Ping Li; Zhi-Hua Li (Science of The Total Environment, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Indole alkaloids isolated from the Nicotiana tabacum-derived Aspergillus fumigatus 0338 as potential inhibitors for tobacco powdery mildew and their mode of actions - Yue-Yu Ma; Gui Pu; Hua-Yin Liu; Sui Yao; Guang-Hui Kong; Yu-Ping Wu; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Qiu-Fen Hu; Feng-Xian Yang (Pesticide Biochemistry and Physiology, 2024)

Cinnamaldehyde treats largemouth bass non-lethal bacterial enteritis by regulating gut morphology, barrier, inflammation, microbiota and serum biochemistry - Ping Ouyang; Shuanghui Huang; Wenyan Wei; Jianing Wu; Yongheng Zhou; Shuhan Li; Qiunan Li; Yi Geng; Xiaoli Huang; Defang Chen; Lizi Yin (Aquaculture, 2024)

Degradation mechanism of antibiotics by flower-like Bi2S3 sensitized anatase/rutile TiO2 coupled with SiO2 photonic crystals - Ruizhen Liu; Huaiyuan Jiang; Ping Li; Jianfei Yin; Zhengrui Xu; Xiaoyu Chen; Jian Cheng; Shuangxi Gu; Renliang Lyu (Journal of Water Process Engineering, 2024)

Efficient recovery of iron from anaerobic roasted cyanide tailings using advanced oxidation technology - Ping Dong; Yonghui Song; Lei Wu; Jin Bao; Ning Yin; Rongyan Zhu; Yifan Li; Hefu Li (Hydrometallurgy, 2024)

Fluctuating redox conditions accelerate the electron storage and transfer in magnetite and production of dark hydroxyl radicals - Dan Li; Jieyi Sun; Yibo Fu; Wentao Hong; Heli Wang; Qian Yang; Junhong Wu; Sen Yang; Jianhui Xu; Yunfei Zhang; Yirong Deng; Yin Zhong; et al. (Water Research, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Community pattern of potential phenanthrene (PHE) degrading bacteria in PHE contaminated soil revealed by 13C-DNA stable isotope probing - Xiufeng Tang; Ye Li; Ruihe Jin; Guoyu Yin; Lijun Hou; Min Liu; Feng Ju; Ping Han (Chemosphere, 2023)

The phosphoproteome is a first responder in tiered cellular adaptation to chemical stress followed by proteomics and transcriptomics alteration - Peiru Chen; Yuan Li; Qi Long; Tao Zuo; Zhenpeng Zhang; Jiabin Guo; Danyang Xu; Kaixuan Li; Shu Liu; Suzhen Li; Jian Yin; Lei Chang; et al. (Chemosphere, 2023)

Deciphering characterization of seasonal variations in microbial communities of marine ranching: Diversity, co-occurrence network patterns, and assembly processes - Chengzhuang Chen; Ping Li; Minghao Yin; Jinxin Wang; Yongjun Sun; Wenming Ju; Ling Liu; Zhi-Hua Li (Marine Pollution Bulletin, 2023)

New dechlorination products and mechanisms of tris(2-chloroethyl) phosphate by an anaerobic enrichment culture from a vehicle dismantling site - Sen Yang; Junhong Wu; Heli Wang; Qian Yang; Huanheng Zhang; Lihua Yang; Dan Li; Yirong Deng; Yin Zhong; Ping'an Peng (Environmental Pollution, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Electronegative graphene film based interface-chemistry regulation for stable lithium metal batteries - Ping Xie; Yumeng Peng; Xianbin Liu; Binze Yang; Fan Yang; Haijie Zhao; Sayed Y. Attia; Xiaoming Xu; Yulong Sun; Yanhong Yin; Yesheng Li; Ziping Wu (Chemical Engineering Journal, 2023)

Association between thermal stress and cardiovascular mortality in the subtropics - Maidina Jingesi; Shuhua Lan; Jing Hu; Mengyi Dai; Suli Huang; Siyi Chen; Ning Liu; Ziquan Lv; Jiajia Ji; Xiaoheng Li; Peng Wang; Jinquan Cheng; et al. (International Journal of Biometeorology, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Promoted iron corrosion and enhanced phosphate removal by micro-electric field driven zero-valent iron - Chunlin Fan; Bing Li; Weiquan Li; Weiting Chen; Weizhao Yin; Ping Li; Jinhua Wu (Chemosphere, 2023)

Relationship of individual and mixed urinary metals exposure with liver function in the China National Human Biomonitoring (CNHBM) of Zhejiang Province - Ping Cheng; Yi Tao; Jinfeng Hu; Hongxin Wang; Ruifang Zhao; Shenghua Mei; Yin Yang; Fugen Ye; Zhijian Chen; Hao Ding; Mingluan Xing; Peiwei Xu; et al. (Chemosphere, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

Geochemical and provenance heterogeneity of small mountainous river systems in Southeast China - Yalong Li; Xiangtong Huang; Ergang Lian; Chao Li; Juan Xu; Ping Yin; Zhen Song; Shouye Yang (Global and Planetary Change, 2023)

Distribution and transformation of potentially toxic elements in crack under coal mining disturbance - Junchi Li; Qinxue Yu; Ruoxi Qian; Xin Xiao; Yan Liang; Ping Luo; Hui Wang; Yin Lu; Lili Xu; Qingfeng Liu; Yu Xiao (Environmental Monitoring and Assessment, 2023)

Formation and isomerization of (Z)-methyl epijasmonate, the key contributor of the orchid-like aroma, during tea processing - Zhihui Feng; Yifan Li; Ping Zhang; Jieqiong Wang; Yongquan Xu; Yingying Feng; Xiaoting Zhai; Xiaogen Yang; Xiaochun Wan; Junfeng Yin (Food Research International, 2023)

Experimental research progress of grid to rod fretting in pressurized water reactors - Yong-jun Jiao; Zheng-yang Li; Zeng-ping Pu; Mei-yin Zheng; Quan-yao Ren; Zhen-bing Cai; Yin-wei Wu; Sui-zheng Qiu (Annals of Nuclear Energy, 2023)

An aggregation-induced emission sensor combined with UHPLC-Q-TOF/MS for fast identification of anticoagulant active ingredients from traditional Chinese medicine - Ziyi Li; Bing Wang; Kunhui Sun; Guo Yin; Ping Wang; Xie-an Yu; Chaofeng Zhang; Jiangwei Tian (Analytica Chimica Acta, 2023)

Temporal framework for the Yanliao Biota and timing of the origin of crown mammals - Zhiqiang Yu; Haibing Wang; Chi Zhang; Liping Dong; Magdalena H. Huyskens; Zexian Cui; Paige Cary; Yankun Di; Yuri Amelin; Gang Li; Qiuli Li; Xiao-Ping Xia; et al. (Earth and Planetary Science Letters, 2023)

Distribution and potential health risks of perfluoroalkyl substances (PFASs) in water, sediment, and fish in Dongjiang River Basin, Southern China - Wang Xu; Shibo Li; Weimin Wang; Ping Sun; Chunyang Yin; Xuxia Li; Liang Yu; Gang Ren; Lin Peng; Fei Wang (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Face mask derived micro(nano)plastics and organic compounds potentially induce threat to aquatic ecosystem security revealed by toxicogenomics-based assay - Yan-Jun Liu; He-Yun Yang; Yan-Yun Hu; Zheng-Hao Li; Hao Yin; Yun-Tian He; Keng-Qiang Zhong; Li Yuan; Xing Zheng; Guo-Ping Sheng (Water Research, 2023)

Highly fractionated Hg isotope evidence for dynamic euxinia in shallow waters of the Mesoproterozoic ocean - Yaowen Wu; Hui Tian; Runsheng Yin; Di Chen; Stephen E. Grasby; Jun Shen; Tengfei Li; Sui Ji; Ping'an Peng (Earth and Planetary Science Letters, 2023)

Determinants affecting the blood mercury levels of preschool children in Shanghai, China: A cross-sectional study - Xi Xu; Yu-Qing Wang; Chen-Yin Dong; Chun-Ping Hu; Li-Na Zhang; Zhen-Yan Gao; Min-Ming Li; Su-Su Wang; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

An improved LSTM-based model for identifying high working intensity load segments of the tractor load spectrum - Chang-kai Wen; Ruo-chen Li; Chun-jiang Zhao; Li-ping Chen; Meng-hua Wang; Yan-xin Yin; Zhi-jun Meng (Computers and Electronics in Agriculture, 2023)

The intramolecular integration of carbonyl and N-nitroamino groups to effectively balance the energy and sensitivity of N-nitroamino-functionalized bisazoles - Jinxiong Cai; Jinya Zhang; Jin Xiong; Rui Li; Teng Fei; Qi Lai; Ping Yin; Siping Pang (Chemical Engineering Journal, 2023)

Overexpression of the Persimmon Abscisic Acid DkUGT3 Gene Alters Plant/Fruit Development in Transgenic Tomato - Juan Wang; Yandan Xu; Zhaonan Yin; Liangyu Peng; Qian Li; Ping Leng (Journal of Plant Growth Regulation, 2023)
Persimmon ( Diospyros kaki Thunb.) contains numerous uridine diphosphate glucosyltransferases (UGT), and their roles in fruit development and quality formation have not been well studied because of limited genetic information. This study investigated a persimmon DkUGT3 which is highly expressed in young fruits and leaves during development. DkUGT3 can catalyze ABA glycosylation to form ABA-GE, thereby reducing free ABA. Tomato with overexpressed (OE) DkUGT3 significantly induces pale green color phenotypes in both transgenic young plants and fruits. DkUGT3 -OE significantly weakens the tomato ABA signaling which affects the expressions of ABA-inducible transcriptional factors (TFs), such as GLK1 and GLK2 and their downstream target genes involved in chlorophyll synthesis, chloroplast development, sugar metabolism and transport, and photosynthesis, thereby impeding leaf and fruit development and quality. Conversely, DkUGT3 -RNAi-treatment recovered the OE tomato fruits from yellowing phenotype to green color. This study found that chlorophyll accumulations and ABA level were increased by DkUGT3 -RNAi-treatment in young persimmon leaves. These results demonstrate that DkUGT3 plays crucial roles in ABA-mediated leaf and fruit development. This study provides new evidence for the regulation of ABA in early development.

Saltwater incursion regulates N2O emission pathways and potential nitrification and denitrification in intertidal wetland - Yinghui Jiang; Guoyu Yin; Ye Li; Lijun Hou; Min Liu; Cheng Chen; Dongsheng Zheng; Han Wu; Dengzhou Gao; Yanling Zheng; Ping Han (Biology and Fertility of Soils, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

A new procedure for separating thallium from geological materials prior to stable isotope ratio determination by MC–ICP–MS - Zhao-Yang Wang; Jie Li; Lu Yin; Le Zhang; Jun-Jie Liu; Neng-Ping Shen; Shuang Yan; Qing-Dian Guan (Chemical Geology, 2023)

Optimizing human endometrial mesenchymal stem cells for maximal induction of angiogenesis - Jie Zhang; Huifang Song; Xuemei Fan; Sheng He; Wenjuan Yin; Zexu Peng; Xiaoyan Zhai; Kun Yang; Hui Gong; Zhijun Wang; Yi Ping; Sanyuan Zhang; et al. (Molecular and Cellular Biochemistry, 2023)

Myrochromanol analogues and trichothecene derivatives from the shellfish-derived fungus Albifimbria verrucaria - Sheng-Tao Fang; Yin-Ping Song; Feng-Ping Miao; Xiu-Li Yin; Nai-Yun Ji (Phytochemistry, 2023)

Quantitative Assessment of Climate Change Impacts on Forest Ecosystems - Dan Liu; Hao Yan; Cheng Long Yu; Shi Ping Yin; Cheng Wei Wang; Li Juan Gong (Forest Science, 2023)
Characterizing and predicting the response of terrestrial ecosystems to global change is part of the fundamental challenges of contemporary ecology and ecological conservation. The assessment of climate change impact on forest ecosystems has rarely used a multi-index fusion method for quantitative evaluation. We used forest distribution, net primary productivity, and vegetation coverage to establish an assessment model of the impact of climate change on forest ecosystems. We analyzed the change characteristics of these indicators in the Heilongjiang Province of China. Our results indicate the following: (1) from 2001 to 2019, the forest area in Heilongjiang Province ranged from 234,000 to 246,000 km2. The forest net primary productivity (NPP) ranged from 4.40 to 5.55 MgC·ha-1·yr-1, and the vegetation coverage ranged from 42.42% to 67.64%. The forest NPP and the vegetation coverage showed a significant upward trend. (2) The values of forest ecological roles were significantly positively correlated with the climatic potential. (3) The contribution rate of climate change to forest ecosystem change was negatively correlated with forest coverage, which varied from 4.79% to 18.07% in different regions (cities) of the province. Study Implications: Assessing the influence of climate on forest ecosystems comprehensively and accurately before the government prepares ecological measures is necessary. However, the responses of vegetation coverage and net primary productivity to climate change may not be consistent, so climate studies that consider forest ecosystem change trends by a single indicator may have confounding results. We established a model for evaluating the impact of climate change on forest ecosystems to solve this problem. This knowledge may provide a reference for the response, adaptation, and vulnerability assessment of forest ecosystems to climate change.

Reliable spectroscopic identification of minerals associated with serpentinization: Relevance to Mars exploration - Wen-Ping Liu; Wei Yin; Bin-Long Ye; Tian-Lei Zhao; Qi-Zhi Yao; Yi-Liang Li; Sheng-Quan Fu; Gen-Tao Zhou (Icarus, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Valorization of lignin through reductive catalytic fractionation of fermented corn stover residues - Wen-Zheng Yin; Ling-Ping Xiao; Shuang-Lin Zou; Wen-Xin Li; Hongliang Wang; Run-Cang Sun (Bioresource Technology, 2023)

Bioaugmentation with Tetrasphaera to improve biological phosphorus removal from anaerobic digestate of swine wastewater - Jiaxin Wang; Chiqian Zhang; Ping Li; Hui Xu; Weiwu Wang; Weizhao Yin; Jinhua Wu; Zhiqiang Hu (Bioresource Technology, 2023)

Sr-Nd isotopic fingerprints of Red River sediments and its implication for provenance discrimination in the South China Sea - Zhifei Duan; Chao Li; Yulong Guo; Nicholas Chia Wei Ng; Shouye Yang; Van Vuong Bui; Dac Ve Nguyen; Xiaoyong Duan; Ping Yin; Thi Thu Trang Tran; Dinh Nam Le; Thi Hong Hanh Nguyen; et al. (Marine Geology, 2023)

Tracking and dating incipient melting of a new grouplet of primitive achondrites - Yun Jiang; Ye Li; Jia Liu; Qing Wang; Li-Ping Qin; Ke Zhu; Shiyong Liao; Zongjun Yin; Yongbo Peng; Piers Koefoed; Weibiao Hsu (Geochimica et Cosmochimica Acta, 2023)

Nitrogen loss from anaerobic ammonium oxidation coupled to Iron(III) reduction activity across estuarine and coastal wetlands of China: Spatial variations, controlling factors, and environmental implications - Shuntao Chen; Dengzhou Gao; Xiaofei Li; Dongyao Sun; Yanling Zheng; Hongpo Dong; Xia Liang; Guoyu Yin; Ping Han; Min Liu; Lijun Hou (CATENA, 2023)

Erratum to: Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Recovery iron from cyanide tailings by anaerobic roasting-persulfate leaching: effect of roasting temperature - Ping Dong; Yonghui Song; Lei Wu; Jin Bao; Ning Yin; Rongyan Zhu; Yifan Li (Environmental Science and Pollution Research, 2023)

Corrigendum to “Dendrobium huoshanense stem polysaccharide ameliorates rheumatoid arthritis in mice via inhibition of inflammatory signaling pathways” [Carbohydr. Polym. 258 (2021) 117657] - Zhen-Zi Shang; Dan-Yang Qin; Qiang-Ming Li; Xue-Qiang Zha; Li-Hua Pan; Dai-Yin Peng; Jian-Ping Luo (Carbohydrate Polymers, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Cyclopentenone and wickerol derivatives from the marine algicolous fungus Trichoderma atroviride A-YMD-9-4 - Xiu-Li Yin; Yin-Ping Song; Xiang-Hong Liu; Nai-Yun Ji (Natural Product Research, 2023)

Effective immobilization of Cd(II) in soil by biotic zero-valent iron and coexisting sulfate - Weiquan Li; Yuhang Yang; Xueying Lin; Weizhao Yin; Zhanqiang Fang; Ping Li; Jinhua Wu (Chemosphere, 2023)

Enhanced Cd(II) immobilization in sediment with zero-valent iron induced by hydrogenotrophic denitrification - Ying Chen; Weiquan Li; Huaitian Bu; Weizhao Yin; Ping Li; Zhanqiang Fang; Jinhua Wu (Journal of Hazardous Materials, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Effects of Electron Donors and Acceptors on Cr(VI) Removal in Biotic Fe0 Columns Preloaded with Microorganisms - Weiquan Li; Mingxi Li; Weizhao Yin; Weinan Zhang; Jiawei Zhong; Ping Li; Hong Deng; Jinhua Wu (Water, Air, & Soil Pollution, 2022)

Isolation, identification, and quantification of triterpene saponins in the fresh fruits of Panax notoginseng - Zheng-yi Qu; He-cheng Wang; Yin-ping Jin; Ya-li Li; Ying-ping Wang (Natural Product Research, 2022)

Comparative transcriptome analyses identify genes involved into the biosynthesis of forsythin and forsythoside A in Forsythia suspensa - Wang Jun Yuan; Su Ping Zhang; Zhi Yin He; Yan Xia He; She Qi He; Li Jun Liu; Xin Sun; Qin Li (Functional & Integrative Genomics, 2022)

Feasibility Studies of Nebulized SARS-CoV-2 Neutralizing Antibody in Mice and Cynomolgus Monkeys - Jilei Jia; Zhaojuan Yin; Xiao Zhang; Huimin Li; Dan Meng; Qianqian Liu; Hongfang Wang; Meng Han; Shixiang Suo; Yan Liu; Ping Hu; Chunyun Sun; et al. (Pharmaceutical Research, 2022)
Purpose Neutralizing antibodies, administrated through intravenous infusion, have shown to be highly efficacious in treating mild and moderate COVID-19 caused by SARS-CoV-2 infection in the lung. However, antibodies do not transport across the plasma-lung barrier efficiently, and up to 100 mg/kg dose was used in human causing significant supply and cost burdens. This study was to explore the feasibility of nebulized antibodies inhalation delivery as an alternative route. Methods HB27, a potent RBD-specific humanized monoclonal antibody (Zhu et al. in National Sci Rev. 8:nwaa297, 2020), showed excellent protection against SARS-CoV-2 in animal model and good safety profile in clinical studies. The pharmacokinetics and preliminary safety of HB27 administrated through the respiratory tract were studied in mice and cynomolgus monkeys here. Results At a single 5 mg/kg dose, the peak HB27 concentration in mice pulmonary epithelial lining fluid (ELF) reached 857.8 μg/mL, 670-fold higher than the PRNT 90 value of 1.28 μg/mL, and maintained above PRNT 90 over 240 h. In contrast, when administrated by intravenous injection at a 5 mg/kg dose, the antibody concentrations in mice ELF were below PRNT 90 value throughout, and were about 50-fold lower than that in the serum. In cynomolgus monkeys administrated with a single dose through inhalation, the antibody concentration in ELF remained high within 3 days. No drug-related safety concerns were observed in the studies. Conclusions The study demonstrated that nebulized neutralizing antibody delivery though inhalation could be a more efficient and efficacious alternative approach for treating COVID-19 and other respiratory infectious diseases, and warrants further evaluation in clinical studies.

Oxytocin Receptor in Cerebellar Purkinje Cells Does Not Engage in Autism-Related Behaviors - Li-Ping Shen; Wei Li; Ling-Zhu Pei; Jun Yin; Shu-Tao Xie; Hong-Zhao Li; Chao Yan; Jian-Jun Wang; Qipeng Zhang; Xiao-Yang Zhang; Jing-Ning Zhu (The Cerebellum, 2022)

Transport process and mechanism of the Hongshiyan rock avalanche triggered by the 2014 Ludian earthquake, China - Shi-lin Zhang; Yue-ping Yin; Hai-bo Li; Wen-pei Wang; Jia-wen Zhou (Landslides, 2022)

Prenatal and postnatal transfer of perfluoroalkyl substances from mothers to their offspring - Yingxue Liu; An Li; Qi An; Kai Liu; Ping Zheng; Shanshan Yin; Weiping Liu (Critical Reviews in Environmental Science and Technology, 2022)

Residential proximity to major roadway and progression in physical disability in older adults in China - Jing Hu; Wenqian Chen; Lei Li; Yu Zhang; Hongwei Jiang; Wenhua Liu; Ping Yin (Environmental Science and Pollution Research, 2022)

Targeting GATA1 and p2x7r Locus Binding in Spinal Astrocytes Suppresses Chronic Visceral Pain by Promoting DNA Demethylation - Yan-Yan Wu; Hai-Long Zhang; Xiaomin Lu; Han Du; Yong-Chang Li; Ping-An Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2022)
Irritable bowel syndrome is a gastrointestinal disorder of unknown etiology characterized by widespread, chronic abdominal pain associated with altered bowel movements. Increasing amounts of evidence indicate that injury and inflammation during the neonatal period have long-term effects on tissue structure and function in the adult that may predispose to gastrointestinal diseases. In this study we aimed to investigate how the epigenetic regulation of DNA demethylation of the p2x7r locus guided by the transcription factor GATA binding protein 1 (GATA1) in spinal astrocytes affects chronic visceral pain in adult rats with neonatal colonic inflammation (NCI). The spinal GATA1 targeting to DNA demethylation of p2x7r locus in these rats was assessed by assessing GATA1 function with luciferase assay, chromatin immunoprecipitation, patch clamp, and interference in vitro and in vivo . In addition, a decoy oligodeoxynucleotide was designed and applied to determine the influence of GATA1 on the DNA methylation of a p2x7r CpG island. We showed that NCI caused the induction of GATA1, Ten-eleven translocation 3 (TET3), and purinergic receptors (P2X7Rs) in astrocytes of the spinal dorsal horn, and demonstrated that inhibiting these molecules markedly increased the pain threshold, inhibited the activation of astrocytes, and decreased the spinal sEPSC frequency. NCI also markedly demethylated the p2x7r locus in a manner dependent on the enhancement of both a GATA1–TET3 physical interaction and GATA1 binding at the p2x7r promoter. Importantly, we showed that demethylation of the p2x7r locus (and the attendant increase in P2X7R expression) was reversed upon knockdown of GATA1 or TET3 expression, and demonstrated that a decoy oligodeoxynucleotide that selectively blocked the GATA1 binding site increased the methylation of a CpG island in the p2x7r promoter. These results demonstrate that chronic visceral pain is mediated synergistically by GATA1 and TET3 via a DNA-demethylation mechanism that controls p2x7r transcription in spinal dorsal horn astrocytes, and provide a potential therapeutic strategy by targeting GATA1 and p2x7r locus binding.

Activating PIK3CA postzygotic mutations in segmental overgrowth of muscles with bone involvement in the body extremities - Wen Tian; Liying Sun; Qi Zhang; Junhui Zhao; Yang Guo; Wenyao Zhong; Liu Liu; Katia Meirelles; Sha Tang; Jing Zhang; Yingzhao Huang; Yuehan Yin; et al. (Molecular Genetics and Genomics, 2022)

Aberrant functional and effective connectivity of the frontostriatal network in unilateral acute tinnitus patients with hearing loss - Gang-Ping Zhou; Yu-Chen Chen; Wang-Wei Li; Heng-Le Wei; Yu-Sheng Yu; Qing-Qing Zhou; Xindao Yin; Yue-Jin Tao; Hong Zhang (Brain Imaging and Behavior, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Geo-structures and deformation-failure characteristics of rockslide areas near the Baige landslide scar in the Jinsha River tectonic suture zone - Shi-lin Zhang; Yue-ping Yin; Xie-wen Hu; Wen-pei Wang; Zong-liang Li; Xin-ming Wu; Gang Luo; Sai-nan Zhu (Landslides, 2021)

Aberrant activity within auditory network is associated with psychiatric comorbidities in interictal migraineurs without aura - Heng-Le Wei; Yu-Chen Chen; Yu-Sheng Yu; Xi Guo; Gang-Ping Zhou; Qing-Qing Zhou; Li-Jie Qu; Xindao Yin; Junrong Li; Hong Zhang (Brain Imaging and Behavior, 2021)

Detoxification of aflatoxin B 1 in broiler chickens by a triple-action feed additive - Hongwei Guo; Juan Chang; Ping Wang; Qingqiang Yin; Chaoqi Liu; Silu Li; Qun Zhu; Mingfan Yang; Xiaofei Hu (Food Additives & Contaminants: Part A, 2021)

Two new selenite reducing bacterial isolates from paddy soil and the potential Se biofortification of paddy rice - Chunlei Huang; Helin Wang; Xinyan Shi; Yanhong Wang; Ping Li; Hanqin Yin; Yixian Shao (Ecotoxicology, 2021)

Modulation of Antioxidant Enzymes, Heat Shock Protein, and Intestinal Microbiota of Large Yellow Croaker (Larimichthys crocea) Under Acute Cold Stress - Huirong Lv; Yanli Liu; Haidong Li; Xiaolong Yin; Ping Wang; Xiaoyu Qu; Yang Gao; Weiye Li; Zhangjie Chu (Frontiers in Marine Science, 2021)
The experiment was conducted in a sealed, temperature-controlled room. The initial water temperature of the treatment group was 12°C, lowered by 1°C a day to 8°C using a chiller, and maintained at that temperature for 3 days. The water temperature was then increased by 1°C per day to 12°C using a heater. The control group were the fish that kept at 12°C at the beginning of the experiment; T1 represents the group that sampled on the first day when the water temperature reached 8 from 12°C; T2 represents the group that sampled when the fish had been kept at 8°C for 3 days; T3 represents the group sampled when the water temperature was increased to 12 from 8°C. The antioxidant abilities of the liver, muscle, and intestine of large yellow croaker at different temperatures and times were determined, and the expression of HSP70 and HSP90 in the liver as well as the changes in intestinal microbiota were investigated. The results showed that the activities of SOD, CAT, GSH-Px, and MDA content increased significantly when the water temperature decreased from 12 to 8°C, significantly higher than those in the control group. The gene expression levels of HSP70 and HSP90 in the liver of large yellow croaker significantly increased under low temperature stress and were significantly higher than those in the control group. The diversity and abundance of intestinal microbiota of large yellow croaker were altered when the water temperature was maintained at 8°C, although the change was not obvious. Proteobacteria, Firmicutes, and Bacteroidetes were the dominate phyla in both the 12 and 8°C groups, and the temperature variation did not change the functional pathways of the microbiota. In conclusion, the acute temperature variation affected the antioxidant ability and heat shock protein expression of large yellow croaker but did not affect the diversity or abundance of the intestinal microbiota. These results will provide a theoretical basis for studying the mechanisms of large yellow croaker overwintering and adaptation to low temperatures.

The sub-inhibitory concentration of cinnamaldehyde resists Aeromonas hydrophila pathogenicity via inhibition of W-pili production - Ping Ouyang; Jiehao Chen; Lizi Yin; Yi Geng; Defang Chen; Kaiyu Wang; Weiming Lai; Hongrui Guo; Jing Fang; Zhengli Chen; Li Tang; Chao Huang; et al. (Aquaculture International, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Emergent chikungunya fever and vertical transmission in Yunnan Province, China, 2019 - XiaoXiong Yin; Ting-Song Hu; HaiLin Zhang; YongHua Liu; ZhiJian Zhou; LeBin Liu; Ping Li; YiYin Wang; ZhaoLan Yang; Jing Yu; SiYu Chen; Fu-Qiang Zhang (Archives of Virology, 2021)

Sediment Characteristics, Sources, and Transport Patterns in Kompong Som Bay, Cambodia: Indications from Grain Size and Heavy Minerals - Jinqing Liu; Xiaoying Chen; Ping Yin; Ke Cao; Fei Gao; Yuanku Meng; Jiandong Qiu; Meina Li (Journal of Ocean University of China, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Assembly of Satsuma mandarin mitochondrial genome and identification of cytoplasmic male sterility–specific ORFs in a somatic cybrid of pummelo - Shuai Zhang; Zhao-Ping Yin; Xiao-Meng Wu; Chao-Chao Li; Kai-Dong Xie; Xiu-Xin Deng; Jude W. Grosser; Wen-Wu Guo (Tree Genetics & Genomes, 2020)

Localization and characterization of Citrus centromeres by combining half-tetrad analysis and CenH3-associated sequence profiling - Qiang-Ming Xia; Lu-Ke Miao; Kai-Dong Xie; Zhao-Ping Yin; Xiao-Meng Wu; Chun-Li Chen; Jude W. Grosser; Wen-Wu Guo (Plant Cell Reports, 2020)

Adult Stress Promotes Purinergic Signaling to Induce Visceral Pain in Rats with Neonatal Maternal Deprivation - Shufen Hu; Qian Sun; Wan-Jie Du; Jian Song; Xin Li; Ping-An Zhang; Ji-Tian Xu; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Chronic visceral pain is one of the primary symptoms of patients with irritable bowel syndrome (IBS), which affects up to 15% of the population world-wide. The detailed mechanisms of visceral pain remain largely unclear. Our previous studies have shown that neonatal maternal deprivation (NMD) followed by adult multiple stress (AMS) advances the occurrence of visceral pain, likely due to enhanced norepinephrine (NE)-β 2 adrenergic signaling. This study was designed to explore the roles of P2X3 receptors (P2X3Rs) in the chronic visceral pain induced by combined stress. Here, we showed that P2X3Rs were co-expressed in β 2 adrenergic receptor (β 2 -AR)-positive dorsal root ganglion neurons and that NE significantly enhanced ATP-induced Ca 2+ signals. NMD and AMS not only significantly increased the protein expression of P2X3Rs, but also greatly enhanced the ATP-evoked current density, number of action potentials, and intracellular Ca 2+ concentration of colon-related DRG neurons. Intrathecal injection of the P2X3R inhibitor A317491 greatly attenuated the visceral pain and the ATP-induced Ca 2+ signals in NMD and AMS rats. Furthermore, the β 2 -AR antagonist butoxamine significantly reversed the expression of P2X3Rs, the ATP-induced current density, and the number of action potentials of DRG neurons. Overall, our data demonstrate that NMD followed by AMS leads to P2X3R activation, which is most likely mediated by upregulation of β 2 adrenergic signaling in primary sensory neurons, thus contributing to visceral hypersensitivity.

Impaired functional connectivity of limbic system in migraine without aura - Heng-Le Wei; Jinan Chen; Yu-Chen Chen; Yu-Sheng Yu; Gang-Ping Zhou; Li-Jie Qu; Xindao Yin; Junrong Li; Hong Zhang (Brain Imaging and Behavior, 2020)

Overexpression of Purinergic P2X4 Receptors in Hippocampus Rescues Memory Impairment in Rats with Type 2 Diabetes - Ping-An Zhang; Qian Sun; Yong-Chang Li; Rui-Xia Weng; Rui Wu; Hong-Hong Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Purinergic receptors have been reported to be involved in brain disorders. In this study, we explored their roles and mechanisms underlying the memory impairment in rats with type 2 diabetes mellitus (T2DM). T2DM rats exhibited a worse performance in the T-maze and Morris water maze (MWM) than controls. Microglia positive for P2X purinoceptor 4 (P2X4R) in the hippocampus were reduced and activated microglia were increased in T2DM rats. Long Amplicon PCR (LA-PCR) showed that DNA amplification of the p2x4r gene in the hippocampus was lower in T2DM rats. Minocycline significantly reduced the number of activated microglia and the mean distance traveled by T2DM rats in the MWM. Most importantly, P2X4R overexpression suppressed the activated microglia and rescued the memory impairment of T2DM rats. Overall, T2DM led to excessive activation of microglia in the hippocampus, partly through the DNA damage-mediated downregulation of P2X4Rs, thus contributing to memory impairment.

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

PX Domain-Containing Kinesin KIF16B and Microtubule-Dependent Intracellular Movements - Bo-jie Li; Hao Chen; Su-su Jiang; Chu-yao Wang; Qin-hui Tuo; Shi-yin Long; Cai-ping Zhang; Duan-fang Liao (The Journal of Membrane Biology, 2020)

Dryland agricultural environment and sustainable productivity - Gou-Xia Li; Bing-Cheng Xu; Li-Na Yin; Shi-Wen Wang; Sui-Qi Zhang; Lun Shan; Sang-Soo Kwak; Qingbo Ke; Xi-Ping Deng (Plant Biotechnology Reports, 2020)

Outbreak of carp edema virus disease in cultured ornamental koi in a lower temperature in China - Ping Ouyang; Yaojia Zhou; Ruixue Yang; Zhuangzhi Yang; Kaiyu Wang; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Li Tang; et al. (Aquaculture International, 2020)

Thermus caldilimi sp. nov., a thermophilic bacterium isolated from a geothermal area - Meng-Meng Li; Wen-Dong Xian; Xiao-Tong Zhang; Yi-Rui Yin; En-Min Zhou; Yi-Ping Ding; Lan Liu; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

The Verticillium dahliae Sho1‐MAPK pathway regulates melanin biosynthesis and is required for cotton infection - Jun‐Jiao Li; Lei Zhou; Chun‐Mei Yin; Dan‐Dan Zhang; Steven J. Klosterman; Bao‐Li Wang; Jian Song; Dan Wang; Xiao‐Ping Hu; Krishna V. Subbarao; Jie‐Yin Chen; Xiao‐Feng Dai (Environmental Microbiology, 2019)
Summary Verticillium dahliae is a soil‐borne fungus that causes vascular wilt on numerous plants worldwide. The fungus survives in the soil for up to 14 years by producing melanized microsclerotia. The protective function of melanin in abiotic stresses is well documented. Here, we found that the V . dahliae tetraspan transmembrane protein VdSho1, a homolog of the Saccharomyces cerevisiae Sho1, acts as an osmosensor, and is required for plant penetration and melanin biosynthesis. The deletion mutant Δ Sho1 was incubated on a cellophane membrane substrate that mimics the plant epidermis, revealing that the penetration of Δ Sho1 strain was reduced compared to the wild‐type strain. Furthermore, VdSho1 regulates melanin biosynthesis by a signalling mechanism requiring a kinase‐kinase signalling module of Vst50‐Vst11‐Vst7. Strains, Δ Vst50 , Δ Vst7 and Δ Vst11 also displayed defective penetration and melanin production like the Δ Sho1 strain. Defects in penetration and melanin production in Δ Sho1 were restored by overexpression of Vst50 , suggesting that Vst50 lies downstream of VdSho1 in the regulatory pathway governing penetration and melanin biosynthesis. Data analyses revealed that the transmembrane portion of VdSho1 was essential for both membrane penetration and melanin production. This study demonstrates that Vst50‐Vst11‐Vst7 module regulates VdSho1‐mediated plant penetration and melanin production in V . dahliae , contributing to virulence.

A new abietane diterpenoid glycoside from ajuga ovalifolia var. calantha - Fan Yang; Hong-Ping Chen; Xiao-Fei Shen; Hu-Lan Chen; Yin Chen; Li-Xia Wang; Hai Zhang; Wen-Ji Zhao; Mei Zhang; Yu-Zhu Tan (Natural Product Research, 2019)

Exotic Spartina alterniflora invasion alters soil nitrous oxide emission dynamics in a coastal wetland of China - Dengzhou Gao; Lijun Hou; Xiaofei Li; Min Liu; Yanling Zheng; Guoyu Yin; Yi Yang; Cheng Liu; Ping Han (Plant and Soil, 2019)

The effect of host plant on the development and larval midgut protease activity of Plutella xylostella (Lepidoptera: Plutellidae) - Aiping Zhao; Xiangqun Yuan; Di Hu; Chunmeng Leng; Yin Li; Ping Wang; Yiping Li (Phytoparasitica, 2019)

DNA methylation and mRNA expression of COL6A3 in antler mesenchyme of female and male reindeer - Jian-Cheng Zhai; Ruo-Bing Han; Sheng-Nan Wang; Qiang-Hui Wang; Yan-Ling Xia; Wei-Shi Liu; Ya-Jie Yin; He-Ping Li (Genes & Genomics, 2019)

Molecular properties and immunomodulatory activities of a water-soluble heteropolysaccharide isolated from Plantago asiatica L. leaves - Jun-Yi Yin; Xin-Yue Huang; Li Wang; Jian-Qi Guo; Ming-Yong Xie; Jian-Yong Wu; Shao-Ping Nie (Natural Product Research, 2019)

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

Neonatal Maternal Deprivation Followed by Adult Stress Enhances Adrenergic Signaling to Advance Visceral Hypersensitivity - Wan-Jie Du; Shufen Hu; Xin Li; Ping-An Zhang; Xinghong Jiang; Shan-Ping Yu; Guang-Yin Xu (Neuroscience Bulletin, 2019)

Land-Use Changes and Human Driving in and Near the Yangtze River Delta from 1995–2015 - Meina Li; Ping Yin; Xiaoyong Duan; Jinqing Liu; Jiandong Qiu; Van Phach Phung (Journal of Ocean University of China, 2018)

Effects of cadmium stress on the antioxidant system and chlorophyll fluorescence characteristics of two Taxodium clones - Ying-Li Ma; Hui-Fang Wang; Ping Wang; Chao-Guang Yu; Si-Qian Luo; Yu-Feng Zhang; Yin-Feng Xie (Plant Cell Reports, 2018)

Solvent effects on quantitative analysis of brominated flame retardants with Soxhlet extraction - Yin Zhong; Dan Li; Xifen Zhu; Weilin Huang; Ping’an Peng (Environmental Geochemistry and Health, 2018)

Update on the clinical application of deep brain stimulation in sleep dysfunction of Parkinson’s disease - Shuang Zou; Yu-Long Lan; Ya-Ping Hu; Xiao-Xue Yin; Wen-Long Liu; Tao Li; Zhanhua Liang (Acta Neurologica Belgica, 2018)

Protective Effect of Moderate Exogenous Electric Field Stimulation on Activating Netrin-1/DCC Expression Against Mechanical Stretch-Induced Injury in Spinal Cord Neurons - Meili Liu; Chuanwei Yin; Zhengtai Jia; Kun Li; Zhifa Zhang; Yuchen Zhao; Xianghui Gong; Xiaoyu Liu; Ping Li; Yubo Fan (Neurotoxicity Research, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Genomic and Transcriptomic Analysis Identified Gene Clusters and Candidate Genes for Oil Content in Peanut (Arachis hypogaea L.) - Xiaohua Wang; Ping Xu; Liang Yin; Yan Ren; Shuangling Li; Yanmao Shi; Thomas D. Alcock; Qing Xiong; Wei Qian; Xiaoyuan Chi; Manish K. Pandey; Rajeev K. Varshney; et al. (Plant Molecular Biology Reporter, 2018)

Effects of Rhizoma Alismatis extract on biochemical indices and adipose gene expression in oleic acid-induced hepatocyte injury in Jian carp (Cyprinus carpio var. Jian) - Jinliang Du; Rui Jia; Li-ping Cao; Weidong Ding; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2018)

Wideband dipole logging based on segment linear frequency modulation excitation - Xue-Shen Cao; Hao Chen; Ping Li; Hong-Bin He; Yin-Qiu Zhou; Xiu-Ming Wang (Applied Geophysics, 2018)

Eriodictyol protects against Staphylococcus aureus-induced lung cell injury by inhibiting alpha-hemolysin expression - He Xuewen; Ouyang Ping; Yuan Zhongwei; Yin Zhongqiong; Fu Hualin; Lin Juchun; He Changliang; Shu Gang; Yuan Zhixiang; Song Xu; Zou Yuanfeng; Li Lixia; et al. (World Journal of Microbiology and Biotechnology, 2018)

Depth treatment of coal-chemical engineering wastewater by a cost-effective sequential heterogeneous Fenton and biodegradation process - Yili Fang; Weizhao Yin; Yanbin Jiang; Hengjun Ge; Ping Li; Jinhua Wu (Environmental Science and Pollution Research, 2018)

Evolutionary relationships of two balitorids (Cypriniformes, Balitoridae) revealed by comparative mitogenomics - Li‐Xia Shi; Chen Zhang; Yin‐Ping Wang; Qiong‐Ying Tang; Patrick D. Danley; Huan‐Zhang Liu (Zoologica Scripta, 2018)
Balitoridae, a family within the Cypriniformes, inhabit torrential mountain streams in Asia. Although they have long fascinated ichthyologists for their numerous adaptations to this tumultuous environment, the evolutionary history of this group remains poorly understood. In this study, we investigate the evolutionary relationships of the balitorids with particular attention to the phylogenetic placement of two balitorid species, Yaoshania pachychulis and Erromyzon kalotaenia . Both species have extremely limited distributions, they are limited to Mt. Dayaoshan of the Pearl River in China and require dedicated conservation plans. However, little is known about their evolutionary relationships to other balitorids. Here, we examined the evolutionary relationships of Y. pachychulis and E. kalotaenia to each other and other balitorids through sequencing the complete mitochondrial genomes of nine balitorid individuals. For the newly sequenced balitorids, the length of the whole mitogenome, gene arrangement and their base composition are similar to those of other bony fishes. Analyses based on these newly sequenced mitogenomes and an additional 50 previously published mitogenomes show that Y. pachychulis and E. kalotaenia cluster as different clade within the subfamily Gastromyzontinae. The genetic distance between these two species ranges from 0.127 ± 0.003 to 0.132 ± 0.004 which is slightly higher than that between some genera (e.g. the distance between Vanmanenia and Metahomaloptera is 0.127 ± 0.004). Therefore, it is reasonable to assign Y. pachychulis and E. kalotaenia to different genera. Phylogenetic signal assessment suggested that ND 1 , ND 4 and ND 5 genes as well as their concatenated subsets perform relatively well in reconstructing the Cobitoidea phylogeny. The divergence time estimation indicated that the balitorids distributed in Mt. Dayaoshan might have originated and evolved following the flattening and uplifting of the Yunnan–Guizhou Plateau during the late Miocene to late Pliocene.

Network analysis of microRNAs, transcription factors, and target genes involved in axon regeneration - Li-ning Su; Xiao-qing Song; Zhan-xia Xue; Chen-qing Zheng; Hai-feng Yin; Hui-ping Wei (Journal of Zhejiang University-SCIENCE B, 2018)

Olivibacter flavus sp. nov., a novel endophytic bacterium isolated from the root of Camellia sinensis - Lei Tian; Tong-Wei Guan; Ling-Ling Yang; Kai-Yang Lu; Bing-Bing Liu; Wei-Xun ChunYu; Min Yin; En-Yuan Li; Yang Ji; Xiao-Ping Zhang; Shu-Kun Tang (Archives of Microbiology, 2017)

Mapping stripe rust resistance gene YrZH22 in Chinese wheat cultivar Zhoumai 22 by bulked segregant RNA-Seq (BSR-Seq) and comparative genomics analyses - Yong Wang; Jingzhong Xie; Huaizhi Zhang; Bingmin Guo; Shunzong Ning; Yongxing Chen; Ping Lu; Qiuhong Wu; Miaomiao Li; Deyun Zhang; Guanghao Guo; Yan Zhang; et al. (Theoretical and Applied Genetics, 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

A live gI/gE-deleted pseudorabies virus (PRV) protects weaned piglets against lethal variant PRV challenge - Yue Yin; Zhiwen Xu; Xiaowan Liu; Ping Li; Fan Yang; Jun Zhao; Yi Fan; Xiangang Sun; Ling Zhu (Virus Genes, 2017)

Repellence of the main components from the essential oil of Glycosmis lucida Wall. ex Huang against two stored product insects - Shan-Shan Guo; Wen-Juan Zhang; Kai Yang; Jun-Yu Liang; Chun-Xue You; Cheng-Fang Wang; Yin-Ping Li; Zhu-Feng Geng; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2017)

NMR solution structure study of one saturated sulphur-containing amides from Glycosmis lucida - Zhu-Feng Geng; Kai Yang; Yin-Ping Li; Shan-Shan Guo; Chun-Xue You; Wen-Juan Zhang; Zhe Zhang; Shu-Shan Du (Natural Product Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Identification of neuron-related genes for cell therapy of neurological disorders by network analysis - Li-ning Su; Xiao-qing Song; Hui-ping Wei; Hai-feng Yin (Journal of Zhejiang University-SCIENCE B, 2017)

Mice lacking myotubularin-related protein 14 show accelerated high-fat diet-induced lipid accumulation and inflammation - Lv Yin; Peng Yong-bo; Yu Meng-Fei; Chen Weiwei; Zhao Ping; Xue Lu; Ma Li-Qun; Cai Congli; Liu Qing-hua; Shen Jinhua (Journal of Physiology and Biochemistry, 2017)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

Effects of salinity on simultaneous reduction of perchlorate and nitrate in a methane-based membrane biofilm reactor - Yin Zhang; Jia-Xian Chen; Li-Lian Wen; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

Expression and functional analysis of two NhaD type antiporters from the halotolerant and alkaliphilic Halomonas sp. Y2 - Yanbing Cui; Bin Cheng; Yiwei Meng; Chunfang Li; Huijia Yin; Ping Xu; Chunyu Yang (Extremophiles, 2016)

Calpain-Dependent ErbB4 Cleavage Is Involved in Brain Ischemia-Induced Neuronal Death - Ying-mei Lu; Yin-ping Gao; Rong-rong Tao; Mei-hua Liao; Ji-yun Huang; Gang Wu; Feng Han; Xiao-ming Li (Molecular Neurobiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

The use of food waste-based diets and Napier grass to culture grass carp: growth performance and contaminants contained in cultured fish - Zhang Cheng; Wing-Yin Mo; Xiang-Ping Nie; Kai-Bing Li; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Sleep education in Hong Kong - Ngan Yin Chan; Siu Ping Lam; Jihui Zhang; Mandy Wai Man Yu; Shirley Xin Li; Albert Martin Li; Yun Kwok Wing (Sleep and Biological Rhythms, 2016)

Protective action of the phyllanthin against carbon tetrachloride-induced hepatocyte damage in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (In Vitro Cellular & Developmental Biology - Animal, 2016)

A Study of 2,3,7,8-Tetrachlorodibenzo-p-dioxin Induced Liver Injury in Jian Carp (Cyprinus carpio var. Jian) Using Precision-Cut Liver Slices - Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Rui Jia; Guo-Jun Yin (Bulletin of Environmental Contamination and Toxicology, 2016)

The roles of methanogens and acetogens in dechlorination of trichloroethene using different electron donors - Li-Lian Wen; Yin Zhang; Ya-Wei Pan; Wen-Qi Wu; Shao-Hua Meng; Chen Zhou; Youneng Tang; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2015)

Neurology of the H1N1 pandemic in Singapore: a nationwide case series of children and adults - Asha Prerna; Jocelyn Y. X. Lim; Natalie W. H. Tan; Mas Suhaila Isa; Helen May-Lin Oh; Norazieda Yassin; Chian-Yong Low; Derrick W. S. Chan; Chia-Yin Chong; Yee-Sin Leo; Angela Li-Ping Chow; Paul Ananth Tambyah; et al. (Journal of NeuroVirology, 2015)

A newly isolated Haloalkaliphilic bacterium from middle–late Eocene halite formed in salt lakes in China - Fan-Wei Meng; Xiu-Qiang Wang; Pei Ni; Gunther Kletetschka; Chun-He Yang; Yin-Ping Li; Yong-Hua Yang (Carbonates and Evaporites, 2015)

Hepatoprotective and antioxidant effects of phyllanthin against carbon tetrachloride-induced liver injury in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (Aquaculture International, 2015)

Heterologous biosynthesis of costunolide in Escherichia coli and yield improvement - Hua Yin; Yi-bin Zhuang; E-e Li; Hui-ping Bi; Wei Zhou; Tao Liu (Biotechnology Letters, 2015)

Liver Stiffness Measurement, Better than APRI, Fibroindex, Fib-4, and NBI Gastroscopy, Predicts Portal Hypertension in Patients with Cirrhosis - Wei Zhang; Liqiong Wang; Lei Wang; Gang Li; Aoshuang Huang; Ping Yin; Zhenhua Yang; Changquan Ling; Lingtai Wang (Cell Biochemistry and Biophysics, 2015)

Genetic diversity and evolution of two capsid protein genes of citrus tristeza virus isolates from China - Guan-Wei Wu; Min Tang; Guo-Ping Wang; Feng-Yin Jin; Zuo-Kun Yang; Li-Jing Cheng; Ni Hong (Archives of Virology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Over-expression of the MxIRT1 gene increases iron and zinc content in rice seeds - Song Tan; Rui Han; Peng Li; Guang Yang; Shuang Li; Peng Zhang; Wei-Bing Wang; Wei-Zhong Zhao; Li-Ping Yin (Transgenic Research, 2015)

Free radical-scavenging activities of oligomeric proanthocyanidin from Rhodiola rosea L. and its antioxidant effects in vivo - Qian Zhou; Zhi-Ping Yin; Lei Ma; Wen Zhao; Hong-Wei Hao; Hui-Ling Li (Natural Product Research, 2014)

ABI-like transcription factor gene TaABL1 from wheat improves multiple abiotic stress tolerances in transgenic plants - Dong-Bei Xu; Shi-Qing Gao; You-Zhi Ma; Zhao-Shi Xu; Chang-Ping Zhao; Yi-Miao Tang; Xue-Yin Li; Lian-Cheng Li; Yao-Feng Chen; Ming Chen (Functional & Integrative Genomics, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Effects of hydraulic retention time and nitrobenzene concentration on the performance of sequential upflow anaerobic filter and air lift reactors in treating nitrobenzene-containing wastewater - Jinhua Wu; Guocai Chen; Jingjing Gu; Weizhao Yin; Mengxiong Lu; Ping Li; Bo Yang (Environmental Science and Pollution Research, 2014)

Analyses of the Similarity and Difference of Global Gene Expression Profiles in Cortex Regions of Three Neurodegenerative Diseases: Sporadic Creutzfeldt-Jakob Disease (sCJD), Fatal Familial Insomnia (FFI), and Alzheimer’s Disease (AD) - Chan Tian; Di Liu; Wei Xiang; Hans A. Kretzschmar; Qing-Lan Sun; Chen Gao; Yin Xu; Hui Wang; Xue-Yu Fan; Ge Meng; Wei Li; Xiao-Ping Dong (Molecular Neurobiology, 2014)

An overview of nowcasting development, applications, and services in the Hong Kong Observatory - Ping-Wah Li; Wai-Kin Wong; Ping Cheung; Hon-Yin Yeung (Journal of Meteorological Research, 2014)

Catechin ameliorates cardiac dysfunction in rats with chronic heart failure by regulating the balance between Th17 and Treg cells - Qi Zhang; Li-qun Hu; Chang-sen Yin; Ping Chen; Hong-qi Li; Xin Sun; Guang Yan (Inflammation Research, 2014)

Chemical composition, antimicrobial and antioxidant activities of essential oil from Ampelopsis megalophylla - Xian-Fei Xie; Jian-Wu Wang; Han-Ping Zhang; Qi-Xiong Li; Bang-Yin Chen (Natural Product Research, 2014)

Profiles, sources, and transport of polycyclic aromatic hydrocarbons in soils affected by electronic waste recycling in Longtang, south China - De-Yin Huang; Chuan-Ping Liu; Fang-Bai Li; Tong-Xu Liu; Cheng-Shuai Liu; Liang Tao; Yan Wang (Environmental Monitoring and Assessment, 2014)

Anchored periplasmic expression (APEx)-based bacterial display for rapid and high-throughput screening of B cell epitopes - Mo Guo; Li-Ming Xu; Bing Zhou; Jie-Chao Yin; Xian-Long Ye; Gui-Ping Ren; De-Shan Li (Biotechnology Letters, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Elevated Plasma Levels of Hypermethylated RASSF1A Gene Sequences in Pregnant Women with Intrahepatic Cholestasis - Ping Yi; Na Yin; Yingru Zheng; Hongmei Jiang; Xinmei Yu; Yaohua Yan; Qiang Liu; Fenglian Xiao; Li Li (Cell Biochemistry and Biophysics, 2013)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Comparative Analysis of Gene Expression Profiles Between Cortex and Thalamus in Chinese Fatal Familial Insomnia Patients - Chan Tian; Di Liu; Qing-Lan Sun; Chen Chen; Yin Xu; Hui Wang; Wei Xiang; Hans A Kretzschmar; Wei Li; Cao Chen; Qi Shi; Chen Gao; et al. (Molecular Neurobiology, 2013)

Transcriptional Regulation of Genes Encoding Key Enzymes of Abscisic Acid Metabolism During Melon (Cucumis melo L.) Fruit Development and Ripening - Yufei Sun; Pei Chen; Chaorui Duan; Pang Tao; Yanping Wang; Kai Ji; Yin Hu; Qian Li; Shengjie Dai; Yan Wu; Hao Luo; Liang Sun; et al. (Journal of Plant Growth Regulation, 2013)

Increasing phosphorus limitation along three successional forests in southern China - Wenjuan Huang; Juxiu Liu; Ying Ping Wang; Guoyi Zhou; Tianfeng Han; Yin Li (Plant and Soil, 2013)

The confirmation of three repeated sequence elements in the 3′ untranslated region of Chikungunya virus - Yu Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Yin-Hui Yang; Qing-Yu Zhu (Virus Genes, 2013)

Tetramethylpyrazine induces G0/G1 cell cycle arrest and stimulates mitochondrial-mediated and caspase-dependent apoptosis through modulating ERK/p53 signaling in hepatic stellate cells in vitro - Feng Zhang; De-Song Kong; Zi-Li Zhang; Na Lei; Xiao-Jing Zhu; Xiao-Ping Zhang; Li Chen; Yin Lu; Shi-Zhong Zheng (Apoptosis, 2013)

A Comparison of the Biological Activities of Human Osteoblast hFOB1.19 Between Iron Excess and Iron Deficiency - Guo-yang Zhao; Li-ping Zhao; Yin-feng He; Guang-Fei Li; Chao Gao; Kai Li; You-jia Xu (Biological Trace Element Research, 2012)

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

Synthesis and studies on antidepressant activity of 2′,4′,6′-trihydroxychalcone derivatives - Xin Sui; Ying-Chun Quan; Yue Chang; Rui-Peng Zhang; Yin-Feng Xu; Li-Ping Guan (Medicinal Chemistry Research, 2012)

Determination of aflatoxins in edible oil from markets in Hebei Province of China by liquid chromatography–tandem mass spectrometry - Li-xin Yang; Yin-ping Liu; Hong Miao; Bin Dong; Na-jing Yang; Feng-qi Chang; Li-xue Yang; Jing-bo Sun (Food Additives & Contaminants Part B-Surveillance, 2011)

Central nervous system regulation of food intake and energy expenditure: role of galanin-mediated feeding behavior - Peng-Hua Fang; Mei Yu; Yin-Ping Ma; Jian Li; Yu-Mei Sui; Ming-Yi Shi (Neuroscience Bulletin, 2011)

Interleukin-6, but Not Soluble Adhesion Molecules, Predicts a Subsequent Mortality from Cardiovascular Disease in Patients with Acute ST-Segment Elevation Myocardial Infarction - Zhen-Xing Fan; Qi Hua; Yin-Ping Li; Rong-Kun Liu; Zheng Yang (Cell Biochemistry and Biophysics, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Mechanism on apparent dip sliding of oblique inclined bedding rockslide at Jiweishan, Chongqing, China - Yueping Yin; Ping Sun; Ming Zhang; Bin Li (Landslides, 2011)

Catastrophic landslides associated with the M8.0 Wenchuan earthquake - Yueping Yin; Wanmo Zheng; Xiaochun Li; Ping Sun; Bin Li (Bulletin of Engineering Geology and the Environment, 2011)

Transgenic barley with overexpressed PTrx increases aluminum resistance in roots during germination - Qiao-yun Li; Hong-bin Niu; Jun Yin; Hong-bo Shao; Ji-shan Niu; Jiang-ping Ren; Yong-chun Li; Xiang Wang (Journal of Zhejiang University-SCIENCE B, 2010)

FLT3 and NPM1 mutations in Chinese patients with acute myeloid leukemia and normal cytogenetics - Lei Wang; Wei-lai Xu; Hai-tao Meng; Wen-bin Qian; Wen-yuan Mai; Hong-yan Tong; Li-ping Mao; Yin Tong; Jie-jing Qian; Yin-jun Lou; Zhi-mei Chen; Yun-gui Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Ubiquitin ligase Smurf1 targets TRAF family proteins for ubiquitination and degradation - Shan Li; Kefeng Lu; Jian Wang; Liguo An; Guiwen Yang; Hui Chen; Yu Cui; Xiushan Yin; Ping Xie; Guichun Xing; Fuchu He; Lingqiang Zhang (Molecular and Cellular Biochemistry, 2010)

Synthesis and evaluation of antiinflammatory activity of substituted chalcone derivatives - Xue-Wu Zhang; Dong-Hai Zhao; Ying-Chun Quan; Liang-Peng Sun; Xiu-Mei Yin; Li-Ping Guan (Medicinal Chemistry Research, 2010)

Applying DNA C-values to evaluate invasiveness of angiosperms: validity and limitation - Guo-Qi Chen; Shui-Liang Guo; Li-Ping Yin (Biological Invasions, 2010)

Protein kinase C regulates neurite outgrowth in spinal cord neurons - Ping Yang; Zhen-Qiang Li; Lin Song; Yu-Qin Yin (Neuroscience Bulletin, 2010)

Sequence characterized amplified regions (SCAR) reveal candidate markers linked to growth traits in the Chinese shrimp Fenneropenaeus chinensis - Yu-Ying He; Ping Liu; Jian Li; Qing-Yin Wang (Fisheries Science, 2009)

Optimization of fermentation conditions for production of xylanase by a newly isolated strain, Penicillium thiersii ZH-19 - Fengjie Cui; Yin Li; Zhiqiang Liu; Hui Zhao; Lifeng Ping; Liying Ping; Yinan Yang; Yaping Xue; Lijiao Yan (World Journal of Microbiology and Biotechnology, 2009)

Quantification of Three Key Enzymes Involved in Artemisinin Biogenesis in Artemisia annua by Polyclonal Antisera-Based ELISA - Qing-Ping Zeng; Xiao-Mei Zeng; Lu-Lu Yin; Rui-Yi Yang; Li-Ling Feng; Xue-Qin Yang (Plant Molecular Biology Reporter, 2009)

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

Microcalorimetric Study on the Effect of Ce3+ on Halobacterium halobium R1 - Yi Liu; Jun Yin; Ran Li; Li Li; Jie Dai; Ye-Zhong Zhang; Ping Shen (Biological Trace Element Research, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

RNA interference of ecto-5′-nucleotidase (CD73) inhibits human breast cancer cell growth and invasion - Xiuling Zhi; Sifeng Chen; Ping Zhou; Zhimin Shao; Li Wang; Zhouluo Ou; Lianhua Yin (Clinical & Experimental Metastasis, 2007)

Generation of genetic engineering monoclonal antibodies against prion protein - Yin-Xia Huang; Jun Han; Chen-Fang Dong; Li Sun; Chen Gao; Xiao-Fan Wang; Lu Han; Wei Zhou; Bao-Yun Zhang; Hui-Ying Jiang; Mi-Fang Liang; Xiao-Ping Dong (Medical Microbiology and Immunology, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)

Isolation of Female-Specific AFLP Markers and Molecular Identification of Genetic Sex in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Jing Li; Si-Ping Deng; Yong-Sheng Tian; Qing-Yin Wang; Zhi-Meng Zhuang; Zhen-Xia Sha; Jian-Yong Xu (Marine Biotechnology, 2007)

Introduction of the PPF1 gene into rice (Oryza sativa L.) results in delayed leaf senescence - Shuangcheng Li; Desuo Yin; Faqiang Wu; Shiquan Wang; Qiming Deng; Youhua Tang; Huaqiang Zhou; Ping Li (Euphytica, 2007)

Identification of a Novel Protein Associated with Envelope of Occlusion-derived Virus in Spodoptera litura Multicapsid Nucleopolyhedrovirus - Chong Yin; Jianxiu Yu; Lihua Wang; Zhaofei Li; Ping Zhang; Yi Pang (Virus Genes, 2003)